Monoterpenoid bisindole alkaloids with intestinal anti-inflammatory activity from Kopsia hainanensis - Jiamin Wang; Niping Li; Zhuoying Lin; Su Nie; Jiabin Huang; Di Zhang; Yiyi Li; Jian Hong; Wencai Ye; Lei Wang (Phytochemistry, 2026)

A novel finite element model of reinforced concrete beam-column joints considering varying axial load - Xingyu Su; Hong Yang; Junhao Li; Jiulin Bai (Engineering Structures, 2026)

Mechanochemical activation of industrial calcium carbide for sustainable synthesis of propargylic alcohols via its nucleophilic reaction with ketones - Hui Xu; Sinan Cheng; Zhengrun Chen; Zihao Su; Hongwei Fan; Yingzhou Lu; Hong Meng; Chunxi Li (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Rainfall modulates the divergent responses of bacterial and fungal communities to naphthalene contamination in soil - Yuntao Zhao; Duo Zhang; Xin Wang; Yong Cui; Ying Guo; Wei Su; Chen Hong; Wenxin Li; Mengwan Lin; Yixiang Chen; Haobo Ya; Jiayu Chen; et al. (Applied Soil Ecology, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

Terpenoids in Euphorbia milii Ch. des Moulins and their anti-rheumatic potential - Hong Yi Su; Meng Yi Deng; Xin Wang; Shuai Huang; Lin Chen; Xian Li Zhou (Phytochemistry, 2026)

Caffeic acid-initiated co-deposited coating of PEI/MOF - 801 on polyethersulfone substrate for high-efficiency antibiotics/salt separation - Beibei Zhang; Cuncun Zhang; Xuefeng Su; Jin Li; Kui Hong; Xiaoli Zhu (Journal of Water Process Engineering, 2026)

Diurnal differences in the effects of heat exposure on renal function: A randomized controlled crossover trial - Jintao Liu; Yuefang Li; Yarui Fan; Xiaojie Zou; Hung Chak Ho; Danfeng Zhang; Jing Zhang; Jian Song; Xu Wang; Xiuxiu Ding; Xiaoyu Jin; Lijuan Qiu; et al. (Environmental Research, 2026)

Brown carbon optical emissions from residential coal combustion in china: Dominance of solvent-insoluble components - Fan Li; Qiaoqiao Wang; Nan Ma; Zechao Hu; Xiaocong Zhao; Ning Yang; Zheng Yang; Guangjin Liu; Yuanwei Zhong; Jiangchuan Tao; Juan Hong; Yaqing Zhou; et al. (Atmospheric Research, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Optimized retrievals of aerosol optical properties from directional polarimetric camera using optimal linear mixture of basis aerosol models supported by the non-negative matrix factorization - Shikuan Jin; Yingying Ma; Deren Li; Wei Gong; Oleg Dubovik; Jin Hong; Zhenghai Liu; Cheng Chen; Zhongting Wang; Tao He; Yunduan Li; Boming Liu; et al. (Remote Sensing of Environment, 2026)

High-throughput nucleic acid extraction using a pipette-tip annular magnetic separator integrated with real-time fluorescent RPA for rapid detection of Burkholderia gladioli pv. cocovenenans - Jiali Wang; Yuting Su; Yaru Chen; Lei Tang; Dongmei Li; Wenchao Du; Yumin Shen; Fangfang Zhou; Hong Duan; Baoguo Sun; Gang Chen; Lingyan Zheng (Food Bioscience, 2026)

Investigation of the regulatory effects of the initial oxidation–reduction potential on lactic acid-producing bacteria in culture and silage fermentation and its metabolic mechanism - Mengxin Li; Yuanjiang Rong; Qiang Yu; Ya Su; Yulong Xi; Yixi Long; Yixiao Xie; Hong Sun; Jun Hao; Fuyu Yang; Yulong Zheng (Bioresource Technology, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Unraveling the role of plastic polymers in PAHs emissions from municipal solid waste incineration: Quantifying contributions, synergy, and source tracers - Shuangxi Zhou; Xinyu Huang; Zhanbo Hong; Yufan Wang; Bin Zhang; Tianyang Su; Jiajia Pu; Tian Zhang; Yanlin Li; Xinran Qiu; Ling Ding; Xian Li; et al. (Journal of Hazardous Materials, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

Continuous Planting Reshapes Root Endophytic Microbes and Drives Growth Decline in Casuarina equisetifolia - Lei Hong; Yuhua Wang; Mingzhe Li; Jianjuan Li; Qingxu Zhang; Miaoen Qiu; Xiaoli Jia; Qingui Su; Wenxiong Lin; Haibin Wang; Zeyan Wu (Indian Journal of Microbiology, 2026)

Numerical study on the thermal–hydraulic behaviors within a 19-pin wire-wrapped fuel assembly in lead-based fast reactors under porous blockage conditions based on four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

Brain-wide mapping and region-specific cellular characterization of Trhr1 reporter-labeled cells in mice using VISoR imaging - Mingrui Zhang; Su Ma; Hanbo Guo; Yuehan Ji; Hong Ni; Rongjing Ge; Yuanyuan Wang; Yong Jiang; Lianjun Li; Yuyang Zhu; Qian Wang; Lingxiao Guo; et al. (Brain Structure and Function, 2026)

Calculating Receptor Occupancy using TMDD Models – What has to be Considered? - Yu Fu; Liang Yang; Hong Su; Ye Yao; Yu Li; Peiming Ma (The AAPS Journal, 2026)

Monomeric and dimeric sesquiterpenoids from Artemisia princeps Pamp and their anti-inflammatory activity - Hong-Xia Li; Si-Yu Bai; Bao-Jun Su; Dong Liang; Ning Li; Gui-Jie Zhang (Phytochemistry, 2026)

Surface charge engineering improves the alkaline resistance of Pseudoalteromonas tetraodonis κ-carrageenase for application in hydrolysis of κ-carrageenan industrial waste residues - Yu Su; Qingsong Hu; Zuman Dou; Tao Hong; Mingjing Zheng; Zhipeng Li; Lijun Li; Zedong Jiang; Hui Ni; Yanbing Zhu (Food Research International, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

Computational-guided semi-rational design to reprogram phospholipase D into industrially robust enzyme - Xiao-Li Kong; Peng Zhang; Zheng-Qiang Qin; Chang Su; Heng Li; Zhen-Ming Lu; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Reactive OPCs in CNS Injury: From Functional Diversity to Therapeutic Translation - Shengnan Wang; Hong Liu; Jiali Li; Yimin Yuan; Ziwei Dai; Zhida Lan; Chao Huang; Xiaojie Wei; Cheng He; Zhida Su; Shangyao Qin (Neuroscience Bulletin, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Non-biodegradable microplastics amplify antibiotic resistance and pathogen spread in bay plastisphere - Zhi-Wei Wei; Huan-Qin Li; Xin-Hong Wang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Modulation of active sites on anaerobic digestion sludge-derived biochar for peroxomonosulfate activation: From batch experiments investigation to pilot scale - Yanshan Wang; Yulin Wu; Hong Su; Wenzhu Wu; Ning Li; Yingjin Song; Beibei Yan; Zhanjun Cheng (Journal of Environmental Chemical Engineering, 2026)

Predictive design of UV-curable bio-based polyurethane acrylate adhesives: Integrating viscoelasticity, adhesion, and controlled degradation - Bowen Xu; Weiyi Wang; Honghu Li; Gaoteng Shi; Hong Jiang; Chang Su; Shaoyu Wang; Tong Wan; Biao Wang; Bowen Cheng (Chemical Engineering Journal, 2026)

Numerical study on the thermo-hydraulic behaviors of the Directionally-Alternated wire-wrapped fuel assembly in lead-cooled fast reactors based on SSTSAS k-ω-k-ε four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Plastisphere denitrification dynamics shaped by soil acidification: Microbial Community and activity responses - Yu-Chen Li; Sha Zhao; Hu Li; Pei-Yuan Xu; Hong-Xia Cui; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Controlled irradiation-engineered low-molecular-weight pectin exhibits high digestive stability and retains prebiotic activity in vivo - Zhipeng Su; Lingtao Kang; Hongbing Wang; Zixuan Li; Hui Wen; Xia Chang; Yujiao Qian; Fan Huang; Xiaopeng Li; Hong-Hui Wang; Gaoyang Li (Food Research International, 2026)

Harnessing Lactiplantibacillus plantarum LW11: A promising bio-preservative for extending cake shelf life through antifungal metabolites - Xuechun Wang; Zhishuo Zhang; Cuihua Chang; Yujie Su; Luping Gu; Yanjun Yang; Hong Sun; Junhua Li (Food Control, 2026)

Optimizing the keratin degradation activity of keratinase via in silico and molecular engineering approaches - Yu-Xin Chen; Xiang-Lan Xi; Chang Su; Meng-Ting Tan; Heng Li; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Systems Microbiology and Biomanufacturing, 2026)

Numerical study on the turbulent heat transfer behaviors of the fuel assembly with spacer wires in lead-based fast reactors based on four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

Onshore winds amplify shipping PM2.5 exposure in a coastal megaport city: Insights from source apportionment and machine learning - Linxuan Li; Tianjiao Dai; Xiaohui Bi; Shaojie Song; Baoshuang Liu; Young Su Lee; Hong Xu; Qili Dai; Jianhui Wu; Yinchang Feng (Journal of Hazardous Materials, 2026)

Aroma in ‘Munage’ Grape Spirits response to different inoculation strategies of H. uvarum/P. fermentans in mixed fermentation with S. cerevisiae - Jia-Qi Wang; Jia-Liang Hu; Qian-Qian Feng; Yang Zhang; Hong-Yan Zhang; Su-Fang Zhang; Yun-Kui Li; Hua-Feng Yang; Guo-Jie Jin (Food Bioscience, 2026)

Histone H3K27 acetylation of slc25a4 mediates triclocarban-induced transgenerational developmental toxicity in zebrafish (Danio rerio) at subthreshold exposure - Yiming Chang; Zijian Su; Xinyi Jiang; Sihan Huang; Jialing Yu; Zhanyou Li; Keke Liu; Zhijian Sha; Lu Yang; Xiaojia Chen; An hong; Yibo Zhang; et al. (Environmental Research, 2026)

Data-driven enhanced multi-scale topology optimization of lattice structures - Quan Li; Shaohui Su; Zhi Hong; Chang Chen; Xiaoyin Gong; Jinda Liao (Engineering Structures, 2026)

Decumbic acid derivatives from soil fungus Lasiodiplodia sp. BG1083 - Hong-Qiao Dai; Xiao-Bing Su; En-Tao Zhou; Wen-Ting Li; Shuang-Shuang Chen; Hui-Yang Cao; Lin Hu; Meng-Yuan Jiang (Natural Product Research, 2026)

Pseudosparassis yunnanensis, gen. et sp. nov. (Sclerotiniaceae, Helotiales, Ascomycota) from Yunnan Province, Southwestern China - Yuan-Hao Ma; Qi Zhao; Li-Mei Huang; Ping Liu; Hong-Mei Chai; Yong-Chang Zhao; Hong-Li Su; Ishika Bera; Wei-Min Chen (Mycological Progress, 2026)

Apigenin in freezing medium improves frozen-thawed sperm quality and fertilization competence of Oura-type Tibetan sheep - Yujie Tang; Hong Wu; Yingang Guo; Xin Zhang; Yanbing Liu; Jinwang Liu; Mingxia Li; Chengtu Zhang; Jianmin Su (Theriogenology, 2026)

Impacts of biogas residual biochar on anaerobic digestion of food waste with different organic loading rate: Methanogenic performance and metabolic pathways - Xunan Li; Siqin Chu; Yuchen Zhang; Yanbo Zhou; Yinglong Su; Dong Wu; Seungkwan Hong; Min Zhan; Bing Xie (Fuel, 2026)

Adding lycopene to the freezing media enhances the quality, antioxidant capacity, and fertilization ability of frozen-thawed Oure-type Tibetan sheep (Ovis aries) sperm - Yujie Tang; Hong Wu; Lidan Liu; Yanbing Liu; Haoqiang Qin; Mingxia Li; Deqing Yan; Chengtu Zhang; Jianmin Su (Cryobiology, 2026)

Multifunctional pomelo peel cellulose/lysine/ZIF-8 porous foam with honeycomb structure: Adsorption performance and mechanism - Haize Su; Weipeng Qiu; Tenggen Hu; Shaohua Luo; Jinling Wu; Xiaowen Zhong; Na Li; Hao Su; Zhizhou Ling; Zhenlin Xu; Hong Wang; Peng Wen (Carbohydrate Polymers, 2026)

PPIL1 promotes hepatocellular carcinoma progression and associates with poor prognosis - Yunyu Wu; Shuqing Jiang; Junming Yu; Hechun Lin; Saihua Zhang; Yizi Jin; Yang Su; Wenjiao Jin; Chao Ge; Qin Geng; Taoyang Chen; Jinjun Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Lasiobelonium sublanceolatum sp. nov. (Solenopeziaceae, Helotiales) from Yunnan, China - Hong‐Li Su; Thilini Chethana Kandawatte Wedaralalage; Kevin David Hyde; Qi Zhao (New Zealand Journal of Botany, 2026)
This study introduces a new species, Lasiobelonium sublanceolatum H.L. Su, K.D. Hyde & Q. Zhao, collected from Yunnan Province, China. This species differs from other members of Lasiobelonium Ellis & Everh. in the morphological characters of its hairs, paraphyses, asci, and ascospores. Phylogenetic analyses based on the combined internal transcribed spacer (ITS), nuclear ribosomal large subunit (LSU) and the two largest subunits of RNA polymerase II ( RPB1 and RPB2 ) sequences of Solenopeziaceae Ekanayaka & K.D. Hyde also support its recognition as a distinct species, sister to the clade including Las. belanense and Las. lonicerae . This study provides illustrations, detailed descriptions, phylogenetic relationships, and a comparative table summarizing the morphological characteristics of all reported Lasiobelonium species. Our findings increase the reported species diversity of Lasiobelonium and provide baseline data for understanding the discomycete diversity in Yunnan Province, China.

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

The DTH8-SD1 pair regulates panicle architecture in rice - Su Su; Jun Hong; Ling Li; Xiaofei Chen; Cai Chen; Jianxin Shi (Theoretical and Applied Genetics, 2026)

COMPASS: A multi-physics coupling platform for safety analysis of lead-cooled fast reactors - Zinan Huang; Yuxing Liu; You-Peng Zhang; Yunxiang Li; Wenjun Hu; Yuping Zhou; Jian Hong; Runsheng Yang; Xin Su (Annals of Nuclear Energy, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Economic optimization scheduling of combined cooling, heat, and power systems utilizing a multi-strategy enhanced PSO algorithm - Beichen Chen; Haoyuan Lv; Wenpeng Hong; Qingyu Su; Jian Li (Swarm and Evolutionary Computation, 2026)

Mechanistic insights into the enhancement of azithromycin biodegradation by extracellular polymeric substances: Roles of metabolic activity, electron transfer, and reactive oxygen species - Jian-Gang Zhou; Ming-Hong Wei; Shi-Jie Wang; Li Chen; Muhammad Wajid Ullah; Hong-Tao Liu; Su Sun (Journal of Hazardous Materials, 2026)

Comprehensive analysis of metabolic response in Arabidopsis thaliana under heavy metal stress by mass spectrometry - Zhongyan Zhou; Donghao Li; Na Wang; Xiujuan Hong; Wen Su; Cheng Guo; Chongsheng He; Lei Yue (Journal of Hazardous Materials, 2026)

Thermal decomposition of lignin under hydrogen atmosphere: A ReaxFF molecular dynamics study - Linjia Yin; Tan Li; Hong Xian; Jing Su; Bingyan Sun; Zhongyang Luo; Heping Li; Muye Feng; Guanqun Luo; Kaige Wang (Fuel, 2026)

Surface reaction regulation for high-voltage and safe quasi-solid-state lithium metal batteries - Zehui Fan; Yuansheng Liu; Hai Su; Sijia Chi; Qiujiang Dong; Yingxin Liu; Li Wang; Quan-Hong Yang; Yunhua Xu (Chemical Engineering Journal, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Anti-Inflammatory Immunoregulatory Effects of Taurocholic Acid Are Mediated by TGR5 - Hong Su; Ziying Zhang; Chenguang Du; Hong Guan; Peifeng Li; Guifang Cao; Caiyun Wang (Bulletin of Experimental Biology and Medicine, 2026)

Occurrence and remediation of chlorinated paraffins in global environmental matrices: Levels, trends, and future prospects - Yongyi Ma; Qianqian Li; Guijin Su; Huangnan Duan; Tieyu Wang; Jong Seong Khim; Seongjin Hong; Bohua Sun; Jing Meng; Bin Shi (Critical Reviews in Environmental Science and Technology, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Short-term ozone exposure and schizophrenia hospitalization risk: temperature modifying effect and greenspace mitigating effect - Chuan Li; Xin Yu; Rong Song; Yanhong Fang; Jiayuan Yang; Zhiyuan Tang; Shaoqi Wang; Xunrong Cheng; Weizhuo Yi; Rubing Pan; Jian Song; Hong Su (Environmental Pollution, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

A method for detecting transgenic rapeseed using pollen collected by Apis mellifera L - Rong Yuan; Miao Wang; Zhen Li; Meiyan Hong; Li Su; Gang Wu; Xinhua Zeng (Transgenic Research, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Eco-friendly taro stem-sourced cellulose/polypyrrole hybrid aerogel: An efficient capture strategy for microplastics removal - Wei-peng Qiu; Hai-ze Su; Hao Su; Shao-hua Luo; Li-shan Lai; Jia-le Zhu; Zhen-lin Xu; Hong Wang; Peng Wen (Chemical Engineering Journal, 2025)

Vacancy or occupancy? A comparative analysis of methods for identifying short-term residential unit vacancy in multi-family housing - Huimin Zhao; Yitong Li; Qiyuan Hong; Nanxi Su; Lihua Rong; Ying Long (Building and Environment, 2025)

The efficient green bio-manufacturing of Vitamin K 2 : design, production and applications - Li-Yang Xu; Yi-bin Qiu; Xiao-mei Zhang; Chang Su; Jing-Song Shi; Zheng-Hong Xu; Hui Li (Critical Reviews in Food Science and Nutrition, 2025)

Effects of photoperiod on survival, growth and germ cell related gene expression of juvenile giant freshwater prawn, Macrobrachium rosenbergii - Jie Wei; Yakun Wang; Kunhao Hong; Cuixue Huang; Xiangxing Nie; Mingwei Liu; Qiaoyan Zhou; Qiyao Su; Zhuang Mai; Bai Liufu; Huarong Li; Xinping Zhu; et al. (Invertebrate Reproduction & Development, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Fine geometric structures and characteristics of present-day activity of the Tianshui–Baoji segment of the West Qinling Fault, northeastern margin of the Tibetan Plateau - Ruihuan Su; Daoyang Yuan; Zhao Wu; Jinchao Yu; Yunsheng Yao; Hong Xie; Lijun Zhang; Yameng Wen; Hao Sun; Yanwen Chen; Hongqiang Li (Journal of Structural Geology, 2025)

Biodegradable and non-biodegradable microplastics affect greenhouse gas emissions through chemical diversity and microbial biodiversity - Ying Guo; Yajuan Tang; Yi Xing; Chen Hong; Wei Su; Wei Wen; Haobo Ya; Jiayu Chen; Han Zhang; Duo Zhang; Wenxin Li; Yixiang Chen; et al. (Journal of Hazardous Materials, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

Synergistic highly sensitive electrochemical detection of enrofloxacin using Eichhornia crassipes-derived carbon dots and molecularly imprinted polymer networks - Chang-Hong Wang; Yi-Yue Tang; Yan-Jun Li; Fu-Lan Xiao; Lian-Di Zhou; Qi-Hui Zhang; Chun-Su Yuan (Journal of Environmental Chemical Engineering, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Segmentation and deformation mechanisms of the North Tuole Shan fault in the Qilian Mountains: Insights from channel steepness index (k) and fault activity - Hongqiang Li; Daoyang Yuan; Qi Su; Guojun Si; Hong Xie; Yameng Wen; Ruihuan Su; Yunsheng Yao; Jinchao Yu; Hao Sun (Geomorphology, 2025)

Mitochondrial DNA leakage and micronucleus formation activate the cGAS–STING pathway in aristolochic acid I-induced nephritis - Yu yang Lei; Yu shi Hu; Yi yi Cao; Jing Xi; Yu ning Ma; Xiao hong Zhang; Qin wen Gao; Ji an Fu; Xin yu Zhang; Li Su; Yang Luan (Food and Chemical Toxicology, 2025)

Catalyzing polysulfides redox reactions by p-d orbital hybridized ZnCoSe with built-in electric field - Zhengwei Yang; Peng Zhou; Tianyu Zhang; Jiali Liu; Ningxi Lu; Dengke Li; Min Liu; Guang Li; Jincang Su; Manfang Chen; Xiukang Yang; Hongbo Shu; et al. (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Biochar alleviates adverse effects of polystyrene microplastics on anaerobic digestion performance of food waste and antibiotic resistance gene propagation - Feng Wang; Ye Li; Linjie Zhang; Yinglong Su; Yan Zhang; Seungkwan Hong; Min Zhan; Bing Xie (Bioresource Technology, 2025)

Response of soil micro-food web and nutrient transfer efficiency to reclamation strategies in mining area - Peng Gao; Xiujuan Zhang; Hong Zhang; Junjian Li; Chao Su; Yong Liu (Plant and Soil, 2025)

Spatiotemporal assessment of land use carbon emission in the Guangdong-Hong Kong-Macao Greater Bay Area:A hybrid static-dynamic model integrated with PLUS - Yingsheng Zheng; Liang Su; Qiuyun Zeng; Shuli Zhou; Shan Li; Haobin Hong; Haoqian Deng; Wenjie Li (Urban Climate, 2025)

Biocontrol mechanism of a newly isolated Streptomyces sp. JL2001 against Ralstonia solanacearum via aerugine - Zixian Zeng; Wei Cao; Hong Pu; Dousheng Wu; Sai Jiang; Meng Su; Yajing Wang; Zhi Wang; Xin Zhao; Juan Li; Shunxiang Li; Lin Jiang (Pesticide Biochemistry and Physiology, 2025)

Converting pig manure into biochar mitigates the antibiotic resistance of vegetable endophytes - Xue Zhou; Jun Ma; Min Qiao; Yin Wang; Zhi-Hong Cao; Jian-Qiang Su; Wan-Ying Xie; Patrick O'Connor; Gang Li (Environmental Pollution, 2025)

Interface enhanced catalytic hydrodeoxygenation of vanillin as a bio-oil model using Ni-based catalysts - Kuan Du; Hong Li; Long Jiang; Kai Xu; Jun Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Chemical Engineering Journal, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Hexavalent chromium and cellular senescence: A comprehensive analysis from chromate-exposed occupational population and chromate-inhaled mouse model - Zhiqiang Ji; Yali Zhang; Guiping Hu; Shiyi Hong; Zekang Su; Qiaojian Zhang; Li Wang; Tiancheng Wang; Shanfa Yu; Qian Bu; Fang Yuan; Xiaojun Zhu; et al. (Journal of Hazardous Materials, 2025)

The Eyes are The Windows To The Soul: Pupillary Changes Reflect The Consolidation of New and Old Memories During Sleep - Wei-Kun Su; Yan-Jia Luo; Fangyuan Li; Hong Jiang; Jing Wang; Ya-Dong Li (Neuroscience Bulletin, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Biogeographic Patterns of Soil Microbial Biomass in Alpine Ecosystems Depend on Local Rather Than Regional Drivers - Kunwei Wang; Xiangjin Shen; Decai Gao; Jonas J. Lembrechts; Mai‐He Li; Beat Frey; Hang Yin; Hongli Pan; Jin Li; Xu Su; Wei Wang; Xiangtao Wang; et al. (Global Ecology and Biogeography, 2025)
Aim Conflicting distribution patterns of soil microbes along the elevation gradient in alpine ecosystems have been suggested based on observations from individual mountains. There remains a lack of biogeographical studies spanning multiple latitudes and climate zones, a scale appropriate to reveal general ecological patterns of soil microbial biomass (SMB) for alpine ecosystems. We conducted a large‐scale sampling campaign along elevational gradients in seven mountains across mainland China and investigated the biogeographical patterns of soil microorganisms and quantified the influencing environmental factors. Location China. Time Period 2019. Major Taxa Studied Seed plant species and soil microorganisms. Methods We sampled aboveground plants and belowground soils along elevational gradients from closed forests located below the alpine treeline up to the upper elevational limit of vegetation in seven mountains. We analysed the distribution patterns of SMB and the ratio of fungi to bacteria (F/B) and quantified four types of environmental factors at local (i.e., plant functional traits, soil physicochemical properties, and topography) and regional (i.e., macroclimate) scales to determine the drivers of microbial biomass in alpine ecosystems. Results We observed a hump‐shaped pattern of SMB along the elevation gradients, with a maximum near the alpine treeline. The soil nutrient status and plant functional traits played the most decisive roles in shaping SMB. Local‐scale environmental factors were more important than regional factors in determining SMB in alpine ecosystems. Main Conclusions Our study suggests that distribution patterns of SMB in alpine ecosystems are closely related to environmental heterogeneity rather than elevation alone. In the context of future temperature rises with global change, soil microbes can more easily track localised changes in microhabitats compared with top‐down effects of macroclimate, indicating that effects of climate warming on soil microbes could possibly be buffered by local environmental factors in alpine ecosystems.

Ran drives pancreatic cancer metastasis by activating the osteopontin-PI3K/AKT-androgen receptor signaling cascade - Lin Deng; Jingyi Ren; Dong Liu; Hong Li; Guang Yang; Kairui Wang; Yang Song; Haichuan Su (Toxicology and Applied Pharmacology, 2025)

Selection and validation of reference genes for gene expression studies of decidualization based on RNA sequencing - Haoyu Yang; Cancan Wang; Wenxuan Li; Xin Su; Mengyuan Li; Qian Li; Xiang-Hong Xu; Liping Jin (Reproductive Biology, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Designing flexible aliphatic linker based molecular imprinted covalent organic framework for rapid and selective extraction and detection of trace zearalenone - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2025)

Effect of alkaline-thermal pretreatment on biodegradable plastics degradation and dissemination of antibiotic resistance genes in co-compost system - Wenyue Wang; Jianping Tao; Ruirui Pang; Linjie Zhang; Yuchen Zhang; Yinglong Su; Weiying Li; Seungkwan Hong; Hyunook Kim; Min Zhan; Bing Xie (Journal of Hazardous Materials, 2025)

Nutrients and metal(loid)s in surface sediments of the Chishui River: A DGT-based assessment of the last natural tributary of the upper Yangtze River (China) - Wei Xia; Tian-Xin Zhang; Xue Li; Yanpeng Gao; Richard W. Jordan; Hong Su; Shi-Jun Jiang; Yang-Guang Gu (Environmental Research, 2025)

Static-disturbance shear properties and failure mechanisms of karst limestone under different hydrochemical corrosions - Zhi Zheng; Ronghua Li; Hong Zheng; Shaojun Li; Guoshao Su; Dingping Xu; Wei Wang (Engineering Geology, 2025)

Aquifer restoration in the Lubei Plain, China: Insights from InSAR and groundwater head monitoring - Guangli Su; Chunbao Xiong; Wei Zhan; Xuechuan Li; Hong Liang; Yu Li (Advances in Space Research, 2025)

Interaction Between Hypoxia-Inducible Factor 1-alpha Gene Polymorphism and Helicobacter pylori Infection on Gastric Cancer in a Chinese Tibetan Population - Su-Hua Li; Yan Li; Meng-Jun Zhang; Qi An; Jia-Nan Tao; Xue-Hong Wang (Biochemical Genetics, 2025)

Role of myostatin promoter mutations in growth and molting regulation of Macrobrachium rosenbergii - Qiyao Su; Jie Wei; Yakun Wang; Bai Liufu; Huarong Li; Zhuang Mai; Kunhao Hong; Qiaoyan Zhou; Tianhui Jiao; Xidong Mu; Lingyun Yu (Frontiers in Marine Science, 2025)
Myostatin ( Mstn ), a negative regulatory factor in myocytes, has garnered significant attention. This study focused on the Mstn gene and its 24-base-pair mutant in the promoter region of the giant freshwater prawn ( Macrobrachium rosenbergii ), aiming to investigate the regulatory roles of Mstn and its mutant in M. rosenbergii . The research provides theoretical insights into the functional mechanisms of Mstn in crustaceans. Spatiotemporal expression patterns revealed Mstn presence throughout embryonic development and in various body tissues, with peak expression during the gastrula stage and in the hepatopancreas. During the molting cycle, Mstn expression levels decreased in the order of post-molt (A phase), pre-molt (D3 phase), and molting (E phase). Knockdown experiments targeting two genotypes within the Mstn promoter region significantly reduced growth rates and extended molting cycles compared to control group. Further trials on the F2 generation confirmed these findings, highlighting that promoter knockdown influenced the expression of three molting-related genes and slowed the growth rate of M. rosenbergii . This study clarifies the functional role of Mstn in crustacean growth and molting, providing a foundation for understanding its regulatory mechanisms and offering potential applications in aquaculture.

Effects of different feeding strategies for the frozen Antarctic krill meal on growth, muscle nutrition, digestive enzyme activity, immunity, molting, and gut microbiota structure of Cherax quadricarinatus - Zhuang Mai; Jie Wei; Yakun Wang; Zhongqiang Zeng; Fubai Liu; Huarong Li; Qiyao Su; Kunhao Hong; Qiaoyan Zhou; Tianhui Jiao; Tianyan Yang; Lingyun Yu (Frontiers in Marine Science, 2025)
To investigate the effect of the frozen Antarctic krill meal (AKM) as an nutritional supplement in Cherax quadracarinatus culturing, an experiment was designed with the following groups: a control group (C) fed with basic feed throughout the experiment; Experimental Group 1 (E1) fed basic feed for 2 d and then compound feed (50% AKM + 50% basic feed) for 1 d; Experimental Group 2 (E2) fed basic feed for 1 d and then compound feed (50% AKM + 50% basic feed) for 1 d; Experimental Group 3 (E3) fed compound feed (50% AKM + 50% basic feed) daily. After 10 weeks of feeding, growth results revealed that both E1 and E2 groups exhibited significantly higher weight gain rate (WGR) and specific growth rate (SGR) compared to groups C and E3 (p < 0.05), with E2 achieving the highest survival rate (SR). Regarding muscle nutrition, the contents of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in C. quadracarinatus muscle showed a gradual increase with higher AKM feeding levels (p < 0.05), while the highest astaxanthin content was observed in group E2. Analysis of digestive enzyme activity and fluorescence quantification demonstrated that feeding AKM every other day (E2) not only enhanced the activities of trypsin and lipase in the hepatopancreas but also upregulated the expression levels of immune-related and molting-related genes (p < 0.05), whereas daily AKM feeding showed no significant improvements. Additionally, AKM feeding influenced the intestinal microbiota structure and abundance, with a notable increase in Bacteroidota phylum abundance in group E2.In conclusion, this study demonstrates that alternate-day AKM feeding (E2) optimizes growth performance, enhances muscle nutritional quality, improves digestive and immune capacities, and modifies intestinal microbiota composition in red claw crayfish. In contrast, daily AKM feeding, while elevating certain nutritional indices (e.g., EPA+DHA), exhibits limited benefits for overall growth performance and physiological function enhancement. Therefore, alternate-day AKM feeding is recommended as a superior strategy, providing scientific evidence for its application in C. quadracarinatus aquaculture.

Multi-layer landscape design of urban spontaneous plant community: A case study in Zhengzhou, China - Wangxin Su; Zeqi Zhai; Wenhui Zhang; Rui Li; Jiayi Li; Yang Liu; Wenqian Jiang; Hong Wei; Nan Guo; Yonghua Li (Urban Forestry & Urban Greening, 2025)

Synergistic effects of lead and copper co-exposure on promoting oxidative stress and apoptosis in the neuronal cells - Di Wu; Desheng Wang; Shuang-Shuang Tan; Yu-Qi Li; Su-Li Hong; Tao Wang; Gang Zheng (Toxicology, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

Non-methane hydrocarbons in the continental seas of China: Spatiotemporal variability, controlling factors, and environmental effects - Li-Min Zhou; Jian-long Li; Hai-Jian Su; Gao-Bin Xu; Jian Wang; Hong-Hai Zhang (Marine Environmental Research, 2025)

Health risks of rare earth elements exposure: Impact on mitochondrial DNA copy number and micronucleus frequency - Shiyi Hong; Yali Zhang; Qiaojian Zhang; Zekang Su; Guiping Hu; Li Wang; Shanfa Yu; Xiaojun Zhu; Guang Jia (Journal of Environmental Sciences, 2025)

Rational design of phospholipase D to enhance thermostability and catalytic activity for efficient biocatalytic phosphatidylserine synthesis - Peng Zhang; Xin-An Mao; Xiao-Li Kong; Jin-Song Gong; Zi-Kai Wang; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Chemistry, 2025)

Effect of compound exposure to snowstorm and cold spell on acute myocardial infarction mortality - Jihong Hu; Zhiwei Li; Jingli Zhu; Qin He; Wenjun Cheng; Qianyao Cheng; Yinguang Fan; Hong Su; Huadong Wang; Zhongliang Bai; Xiuya Xing; Jian Cheng (Environmental Research, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Thioclava kandeliae sp. nov., Isolated from the Rhizosphere Soil of Mangrove Plant Kandelia candel - Tong Mou; Jing Su; Jing Zhang; Li-Yan Yu; Hua-Hong Chen; Yu-Qin Zhang (Current Microbiology, 2025)

Fabrication of oat β-glucan-starch composite systems by sequential extraction as batters for deep-fried mushrooms to prevent oil penetration - Yanan Wang; Qifeng Wang; Xueying Shi; Shuanglong Yang; Jianan Chen; Tao Hong; Hui Ni; Tiejing Li; Wentao Su; Yuxiao Wang (Food Chemistry, 2025)

Exploring anxiolytic peptides derived from walnut protein by an integrated approach of multivariate analysis, random forest methodology - Zishan Hong; Ying Cheng; Mingjie Zhou; Shuguang Wang; Xiaomin Li; Shiyun Feng; Guowan Su; Lin Zheng; Mouming Zhao (Food Bioscience, 2025)

Advanced sustainable triboelectric nanogenerators for biomedical and clinical applications: In vivo treatments, in vitro therapeutics, and assisted rehabilitations - Yijun Hao; Xiaopeng Zhu; Keke Hong; Xiangqian Lu; Jiayu Su; Zhao Guo; Zhipeng Wang; Yong Qin; Hongke Zhang; Chuguo Zhang; Xiuhan Li (Chemical Engineering Journal, 2025)

Long-term plastic film mulching promotes microplastic accumulation and alters gross nitrogen transformation in soil - Jinrui Zhang; Kai Wang; Tianxiang Hao; Jinbo Zhang; Christoph Müller; Perrine Florent; Hong Yan; Siyang Ren; Kaijing Qu; Kaige Ren; Jingjing Li; Yiting Su; et al. (Applied Soil Ecology, 2025)

Coastal redox shifts over the past 167 years and preservation of total organic carbon and total nitrogen - Yang-Guang Gu; Hai-Song Li; Hong Su; Richard W. Jordan; Rui-Ze Liang; Shi-Jun Jiang (Marine Pollution Bulletin, 2025)

Semi-sacrificial fabrication of binder-free lithium-aluminum layered double hydroxides adsorbents for lithium extraction - Jinqiang Gao; Mei Hong; Jiatao Zhong; Shengnan Na; Yuqing Su; Han Li; Mingyu Hu; Shihe Yang (Desalination, 2025)

Advances in electrooxidation pathways for the production of carboxylic acids from bio-alcohols - Yi Zhang; Jing Su; Tan Li; Linjia Yin; Hong Xian; Kaige Wang (Chemical Engineering Journal, 2025)

Susceptibility of Soil Elements to Biotic and Abiotic Factors in a Forest-Steppe Ecotone - Qiuhua Li; Jiayun Zhang; Chunbo Li; Hong Ji; Xiaomeng Ma; Peng He; Lixin Yu; Mengfan Zhou; Ning Dang; Jishuai Su; Ruzhen Wang; Heyong Liu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Research on vortex-induced vibration of elliptic cylinder at different inclination angles - Meng-Tian Song; Yan-Hong Li; Su-Xiang Guo; Hai-Long Xu; Jie-Chao Lei; Chien-Cheng Chang (Ocean Engineering, 2025)

Intelligent sensing platform based on europium-doped carbon dots for dual-functional detection of ciprofloxacin/Ga3+ and its tracking in vivo - Le Liang; Su-qian Cai; Yan-li Leng; Chan Huang; Yong-qing Liu; Ye Wang; Li Luo; Mei Han; Xiao-hong Li; Xiao-hua Cai (Journal of Hazardous Materials, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Genome-wide identification and functional characterization of CLG family genes reveal likely roles in epidermal development in Arabidopsis - Qiuli Zhang; Tao Hong; Tian Su; Qiaolong Li; Aoni Xiang; Xinlong Chen; Guanghua He; Fangming Zhao; Renhong Wu (Plant Cell Reports, 2025)

Emerging role of adaptive immunity in diabetes-induced cognitive impairment: from the periphery to the brain - Genhui Yang; Runtao Su; Jie Bu; Ying Li; Xueling Lin; Jiahui Jin; Yanjun Zhang; Pengwei Zhuang; Hong Guo; Qingsheng Yin (Metabolic Brain Disease, 2025)

Outdoor light at night exposure was associated with hypothyroidism in pregnant women: A national study in China - Hong-Xing Zou; Li-Wen Hu; Zheng Zhang; Alexander E.P. Heazell; Xueran Wang; Wentao Yue; Xiao-Fan Lu; Xiao-Yi Liu; Shuo Zhang; Le-Bing Wang; Enjie Zhang; Shaofei Su; et al. (Science of The Total Environment, 2025)

Identifying priority conservation areas for threatened amphibian habitats in the Yangtze river Delta region to maintain regional biodiversity - Zhenya Li; Fanhua Kong; Michael Meadows; Haiwei Yin; Hong S. He; Jie Su; Kejing Zhou (Journal of Environmental Management, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Development of a platform strain for integration expression of phospholipase D and its application in improving phosphatidylserine content of egg yolk - Peng Zhang; Xiao-Li Kong; Jin-Song Gong; Zhi-Yuan Yao; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2025)

Characterization of the complete genome of a novel allexivirus infecting Sauropus androgynus in China - Li-Juan Zhu; Lan-Yi Su; Xing Chen; Shifang Pan; Fagang Xia; Yan-Hong Han; Zhongtian Xu; Qian Xu (Archives of Virology, 2025)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Calixarene incorporated molecular imprinting on covalent organic framework for supramolecular recognition and specific extraction of citrinin - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Tracking chemical feature releases from plastic food packaging to humans - Weikun Meng; Qianyu Chen; Yayun Zhang; Hao Sun; Jianhua Li; Hong Sun; Chunsheng Liu; Mingliang Fang; Guanyong Su (Journal of Hazardous Materials, 2024)

Association between the levels of toxic heavy metals and schizophrenia in the population of Guangxi, China: A case-control study - Bing Shen; Rumei Lu; Miao Lv; JieWen Chen; Jiale Li; Jianxiong Long; Hong Cai; Li Su; Zukang Gong (Environmental Pollution, 2024)

Exceptional heatwaves and mortality in Europe: Greater impacts since the coronavirus disease 2019 outbreak - Zhiwei Li; Yinguang Fan; Zhiwei Xu; Hung Chak Ho; Shilu Tong; Cunrui Huang; Zhongliang Bai; Yiming Gai; Wenjun Cheng; Jihong Hu; Yufan Feng; Hao Zheng; et al. (Environmental Pollution, 2024)

High-level extracellular expression of phospholipase D by combinatorial fine-tuning strategy in Bacillus subtilis for efficient biosynthesis of phosphatidic acid - Peng Zhang; Xin-An Mao; Jin-Song Gong; Xiao-Li Kong; Chang Su; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2024)

Unveiling the overlooked small-sized microbiome in river ecosystems - Fang-Zhou Gao; Li-Xin Hu; You-Sheng Liu; Lu-Kai Qiao; Zi-Yin Chen; Jian-Qiang Su; Liang-Ying He; Hong Bai; Yong-Guan Zhu; Guang-Guo Ying (Water Research, 2024)

Super-large diameter slurry shield tunnel encountering boulder formation: Detection, treatment and data analysis - Wei-Hong Yang; Dong Su; Xing-Tao Lin; Zhi-Jia Lv; Zhan-Hu Yao; Hui Li; Ya-Zhou Zhang; Xiang-Sheng Chen (Transportation Geotechnics, 2024)

Shale gas leakage and fault activation: Insight from the 2021 Luxian MS 6.0 earthquake, China - Zhaofei Liu; Zhi Chen; Ying Li; Zhidan Zhao; Shunying Hong; Le Hu; Ling Ma; Chang Lu; Yuanxin Zhao; Hongyi He; Shujuan Su; Ying Zhao; et al. (Tectonophysics, 2024)

Manure application enriches phage-associated antimicrobial resistance and reconstructs ecological network of phage-bacteria in paddy soil - Jia-Ying Wang; Xin-Li An; Hong-Mei Zhang; Jian-Qiang Su (Soil Biology and Biochemistry, 2024)

Arsenic(III) sequestration by terrestrial-derived soil protein: Roles of redox-active moieties and Fe(III) - Lujian Lin; Bo Yuan; Shengjie Wu; Manlin Su; Hanyi Li; Xiaoting Zhang; Guanglong Zhang; Hualong Hong; Haoliang Lu; Jingchun Liu; Chongling Yan (Journal of Hazardous Materials, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Acid-Resistant bioorthogonal quantum nanoprobes for noninvasive NIR-II imaging of simulated microgravity-induced gastric bacterial alterations in rats - Yiyang Du; Mengyao Su; Weicheng Yang; Zhujun Wu; Yuankun Zhao; Tingjun Yan; Naiqing Li; Yudi Pang; Yingying Li; Hong Ma; Zhimin Wang; Yulin Deng; et al. (Chemical Engineering Journal, 2024)

Fabrication of thermo-responsive microcapsule pesticide delivery system from maleic anhydride-functionalized cellulose nanocrystals-stabilized pickering emulsion template - Jun Li; Chao Wu; Hong-jun Xu; Jia-wei Ding; Yong-jiang Li; Hui Jiang; Hui-fen Su; Sheng Chen; Xin Li; Muhammad Asif Javaid; De-qiang Li (Carbohydrate Polymers, 2024)

Estimation of Regional Evapotranspiration Based on the Decouple Model and Remote Sensing Information ——a Case Study in Beijing City and Nearby Region - Su-Chuang Di; Zhao-Liang Li; Yanmin Ren; Meng Liu; Ya-Zhen Jiang; Fan-Dong Zheng; Xue-Min Li; Yan-Bing Qi; Hong-Lu Liu; Ronglin Tang (International Journal of Remote Sensing, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Radar vegetation indices for monitoring surface vegetation: Developments, challenges, and trends - Xueqian Hu; Li Li; Jianxi Huang; Yelu Zeng; Shuo Zhang; Yiran Su; Yujiao Hong; Zixiang Hong (Science of The Total Environment, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Lappanolides A−N, fourteen undescribed sesquiterpenoids from Saussurea costus (Syn. Saussurea lappa) and their anti HBV activity - Hong-Bo Li; Shi-Qun Bai; Teng-Yun Shu; Qiong Wang; Hao Chen; Li-Hua Su; Min Xu (Phytochemistry, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Segmentation of beach plastic fragments’ contours based on self-organizing map and multi-shape descriptors: A rapid indication of fragmentation and wearing types - Lei Su; Xinyue Dong; Junjie Peng; Hong Cheng; Nicholas J. Craig; Bo Hu; Juan-Ying Li (Journal of Hazardous Materials, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Fenton chemistry activation in metal-organic frameworks for synergistic bacteria eradication - Jiayi Qin; Jia Su; Hong Li; Ling Zhang; Ling Zhang; Ke Jiang (Chemical Engineering Journal, 2024)

UV light absorption at 370 nm by mineral dust, organic carbon, and elemental carbon in the Himalayas and Tibetan Plateau - Chong-Shu Zhu; Yao Qu; Yue Zhou; Nan Wang; Hong Huang; Ting Zhang; Xiao-Li Su; Jun-Ji Cao (Atmospheric Environment, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

Development of Extubation Success Prediction Model for Mechanically Ventilated Patients with Spontaneous Cerebellar Hemorrhage - Yao Jiang; Yue Yu; Jing Fan; Lei Zhang; Yang Ye; Ying-hong Hu; Li-da Su (The Cerebellum, 2024)

Co2+ coordination-assisted molecularly imprinted covalent organic framework for selective extraction of ochratoxin A - Li-Hong Su; Hai-Long Qian; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Acesulfame potassium triggers inflammatory bowel disease via the inhibition of focal adhesion pathway - Zhaodong Zhai; Yibo Zhang; Xujing Liang; Jingsheng Li; Zhiqi Chen; Jianbin Zhang; WeiCai Li; Teng Wang; Qianyi He; Fu Li; Qilin Meng; Jieqiong Cao; et al. (Journal of Hazardous Materials, 2024)

Does the morphology of residential greenspaces contribute to the development of a cardiovascular-healthy city? - Rubing Pan; Weiqiang Wang; Ning Wei; Li Liu; Weizhuo Yi; Jian Song; Jian Cheng; Hong Su; Yinguang Fan (Environmental Research, 2024)

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Enhancing U(VI) removal from highly acidic wastewater through the synergistic effect of diethylenetriaminepenta(methylenephosphonic) acid and meso-SiO2 on nanosized γ-Fe2O3 - Hong Li; Diyun Chen; Weixing Han; Jun He; Gang Song; Lingjun Kong; Minhua Su (Chemical Engineering Journal, 2024)

Cyanidin prevents cardiomyocyte apoptosis in mice after myocardial infarction - Deng Gang; Ouyang Qing; Yongzheng Yang; Muqaddas Masood; Yu-Hong Wang; Jiang Linhui; Su Haotao; Ge Li; Chi Liu; Moussa Ide Nasser; Ping Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Paddy rice methane emissions, controlling factors, and mitigation potentials across Monsoon Asia - Hong Zhou; Fulu Tao; Yi Chen; Lichang Yin; Yibo Li; Yicheng Wang; Chenfang Su (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Mechanisms and clinical landscape of N6-methyladenosine (m6A) RNA modification in gastrointestinal tract cancers - Dan-Hua Zhu; Kun-Kai Su; Xiao-Xi Ou-Yang; Yan-Hong Zhang; Xiao-Peng Yu; Zu-Hong Li; Seyedeh-Sara Ahmadi-Nishaboori; Lan-Juan Li (Molecular and Cellular Biochemistry, 2024)
Epigenetics encompasses reversible and heritable chemical modifications of non-nuclear DNA sequences, including DNA and RNA methylation, histone modifications, non-coding RNA modifications, and chromatin rearrangements. In addition to well-studied DNA and histone methylation, RNA methylation has emerged as a hot topic in biological sciences over the past decade. N6-methyladenosine (m6A) is the most common and abundant modification in eukaryotic mRNA, affecting all RNA stages, including transcription, translation, and degradation. Advances in high-throughput sequencing technologies made it feasible to identify the chemical basis and biological functions of m6A RNA. Dysregulation of m6A levels and associated modifying proteins can both inhibit and promote cancer, highlighting the importance of the tumor microenvironment in diverse biological processes. Gastrointestinal tract cancers, including gastric, colorectal, and pancreatic cancers, are among the most common and deadly malignancies in humans. Growing evidence suggests a close association between m6A levels and the progression of gastrointestinal tumors. Global m6A modification levels are substantially modified in gastrointestinal tumor tissues and cell lines compared to healthy tissues and cells, possibly influencing various biological behaviors such as tumor cell proliferation, invasion, metastasis, and drug resistance. Exploring the diagnostic and therapeutic potential of m6A-related proteins is critical from a clinical standpoint. Developing more specific and effective m6A modulators offers new options for treating these tumors and deeper insights into gastrointestinal tract cancers.

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Multi-perspective interpretation for one-dimensional conventional neural network model to identify iron-bearing waste material - Chenglin Yan; Shu Liu; Zhixiu Zhu; Hong Min; Qingjian Zhang; Wenya Zhao; Piao Su; Yarui An; Chen Li; Xiaohong Wu (Journal of Environmental Chemical Engineering, 2024)

Systematic engineering for efficient production of nicotinamide mononucleotide from d-xylose and nicotinamide in Escherichia coli - Chang Su; Lin Cheng; Jin-Song Gong; Heng Li; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Identification of a cinnamoyl-CoA reductase from Cinnamomum cassia involved in trans-cinnamaldehyde biosynthesis - Peng Ye; Jianmu Su; Jianhao Lin; Yanqun Li; Hong Wu (Planta, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Effect of torrefaction atmospheres on the pyrolysis and combustion of torrefied municipal solid waste - Xiaochao Zhu; Songjiang Li; Yanshan Wang; Shengquan Zhou; Jian Li; Hong Su; Yunan Sun; Beibei Yan; Guanyi Chen (Fuel, 2024)

Cellular senescence mediates hexavalent chromium-associated lung function decline: Insights from a structural equation Model - Yali Zhang; Guiping Hu; Qiaojian Zhang; Shiyi Hong; Zekang Su; Li Wang; Tiancheng Wang; Shanfa Yu; Fang Yuan; Xiaojun Zhu; Guang Jia (Environmental Pollution, 2024)

Understanding hydropyrolysis mechanism of β-O-4 type lignin dimer - Linjia Yin; Muye Feng; Tan Li; Jing Su; Hong Xian; Xiangkun Zhang; Huiyuan Wang; Heping Li; Kaige Wang (Chemical Engineering Journal, 2024)

A novel capacitively coupled contactless conductivity detection (C4D) microfluidic chip integrated 3D microelectrodes for on-site determination of soil nutrients - Yan Hong; Le Wang; Jingming Su; Rujing Wang; Junqing Zhang; Yang Liu; Hongyan Guo; Mengya Li; Qinwen Lu; Yongjia Chang; Jiabao Zhang; Xiangyu Chen (Computers and Electronics in Agriculture, 2024)

Eudesmane sesquiterpenoids with inhibitory effects on NO production from Artemisia princeps - Hong-Xia Li; Ning Diao; Ya-Jie Hu; Su-Juan Wang; Dong Liang; Gui-Jie Zhang (Phytochemistry, 2024)

Integrating molecular imprinting into flexible covalent organic frameworks for selective recognition and efficient extraction of aflatoxins - Li-Hong Su; Hai-Long Qian; Cheng Yang; Chuanxi Wang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Effect of NaClO disinfectant treatment on the yields, components and combustion characteristics of typical medical waste pyrolysis products - Tong Zhang; Aijun Li; Yongda Huang; Su Lei; Muhammad Usman; Yuhang Zheng; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Association between prenatal exposure to per- and polyfluoroalkyl substances and infant anthropometry: A prospective cohort study - Jincan Li; Xiujuan Su; Yan Zhou; Honglei Ji; Zhenzhen Xie; Songlin Sun; Ziliang Wang; Wei Yuan; Maohua Miao; Hong Liang (International Journal of Hygiene and Environmental Health, 2024)

Detection of adulteration of cumin powder by front-face synchronous fluorescence spectroscopy: The influence of the natural variation of adulterants - Jin Tan; Jia-Yuan Liu; Hong Su; Xiao-Han Yang; Hui-Fen Li (Food Control, 2024)

Arsenic disturbs neural tube closure involving AMPK/PKB-mTORC1-mediated autophagy in mice - Xiujuan Li; Gexuan Li; Shuo Cui; Yue Hou; Zelin Li; Ziyi Yan; Tingjuan Huang; Taoran Zhao; Hongkai Su; Bingrui Zhou; Juan Zhang; Ruifang Ao; et al. (Food and Chemical Toxicology, 2024)

SERS lateral flow strip detection of serum biomarkers for noninvasive assessment of operative microwave ablation outcomes of unresectable hepatocellular carcinoma - Xiaoming Su; Xinyu Liu; Yuzhen Ouyang; Yangcenzi Xie; Mingyang Chen; Pan Chen; Jia Liu; Minghua Wu; Chien-hong Lin; Hong Zhong; Ming Li (Chemical Engineering Journal, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Four uncommon cycloamphilectane-type diterpenoids with antibacterial activity from the South China Sea soft coral Sinularia brassica - Zi-Yi Xia; Man-Man Sun; Yang Jin; Ming-Zhi Su; Song-Wei Li; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Establishment of in vitro pollen germination system in C4 model plant Foxtail Millet - Min Su; Dan Wang; Zi-Dong Li; Jian-Hong Hao; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Potential mechanisms of lung injury and repair after hexavalent chromium [Cr(VI)] aerosol whole-body dynamic exposure - Changmao Long; Zekang Su; Guiping Hu; Qiaojian Zhang; Yali Zhang; Tian Chen; Shiyi Hong; Li Su; Guang Jia (Chemosphere, 2024)

Long-term seawall barriers lead to the formation of an urban coastal lagoon with increased antibiotic resistome - Shu-Yi-Dan Zhou; Kai Yang; Roy Neilson; Hu Li; Hong-Zhe Li; Yan-Yan Zhou; Juxiu Liu; Jian-Qiang Su; Fu-Yi Huang (Journal of Environmental Management, 2024)

Study on the suppression characteristics and mechanism of ABC powder on pulverized coal explosion based on the analysis of thermal decomposition characteristics and reaction kinetics - Bingyou Jiang; Qi Yao; Mingqing Su; Jingjing Li; Kunlun Lu; Dawei Ding; Han Hong (Process Safety and Environmental Protection, 2024)

Unveiling the metal mutation nexus: Exploring the genomic impacts of heavy metal exposure in lung adenocarcinoma and colorectal cancer - Mengyuan Liu; Yuting Hong; Xiaohong Duan; Qiming Zhou; Jing Chen; Siyao Liu; Junyan Su; Li Han; Jiali Zhang; Beifang Niu (Journal of Hazardous Materials, 2024)

Iron plaque formation and its influences on the properties of polyethylene plastic surfaces in coastal wetlands: Abiotic factors and bacterial community - Xiaoting Zhang; Lujian Lin; Hanyi Li; Shanle Liu; Shuai Tang; Bo Yuan; Hualong Hong; Manlin Su; Jingchun Liu; Chongling Yan; Haoliang Lu (Journal of Hazardous Materials, 2024)

Centennial-scale source shift in potentially toxic metal(loid)s in Yangtze River - Hualong Hong; Lu Qian; Shengjie Wu; Liyang Ruan; Hanyi Li; Manling Su; Binghuang Zhang; Jingchun Liu; Chongling Yan; Haoliang Lu (Journal of Hazardous Materials, 2024)

Uranium recovery from weakly acidic wastewater using recyclable γ-Fe2O3@meso-SiO2 - Hong Li; Juexi Song; Chuqin Ma; Congjie Shen; Miaoling Chen; Diyun Chen; Hongguo Zhang; Minhua Su (Journal of Environmental Management, 2024)

Facile construction of tourmaline@MOFs composites via micron-scale electrical polarization to enhance photodegradation of gaseous formaldehyde - Jia He; Xin Yu; Xinqi Luan; Hong Li; Syed Jalil Shah; Weige Su; Zhaowei Jia; Jianmin Chen; Liqin Zhou; Jiguang Deng; Zhongxing Zhao; Zuqiang Huang; et al. (Chemical Engineering Journal, 2024)

Establishment of a tilapia lake virus (TiLV)-susceptible cell line for anti-TiLV Chinese herbal compound screening - Song Zhu; Bo Miao; Yu-Zhou Zhang; Qin Yang; Xun-Teng Deng; Li-Hong Gao; Ji-Shu Zheng; De-Cheng Pu; De-Shou Wang; Sheng-Qi Su (Aquaculture, 2023)

A modified COMFA model for elderly people in outdoor environments - Xianjing Su; Yang Li; Chujian Gu; Zhixin Liu; Bin Yang; Bo Hong (Sustainable Cities and Society, 2023)

Association between ambient air pollution and thyroid hormones levels: A systematic review and meta-analysis - Jintao Liu; Kefu Zhao; Tingting Qian; Xuanxuan Li; Weizhuo Yi; Rubing Pan; Yuee Huang; Yifu Ji; Hong Su (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Cleaning performance improvement of a cone filter cartridge using a Venturi nozzle - Quanquan Wu; Zhenqiang Xing; Jianfang Zhong; Qing Wu; Zhengtong Su; Jianlong Li; Hong Huang; Zhifei Ma; Daishe Wu (Process Safety and Environmental Protection, 2023)

Lidocaine pretreatment attenuates inflammatory response and protects against sepsis-induced acute lung injury via inhibiting potassium efflux-dependent NLRP3 activation - Kai Su; Xin-Tao Li; Fang-Xiao Hong; Mu Jin; Fu-Shan Xue (Inflammation Research, 2023)

Effects of Sn-2-palmitate-enriched formula feeding on infants’ growth, stool characteristics, stool fatty acid soap contents and bone mineral content: A systematic review and meta-analysis of randomized controlled trials - Zheqing Zhang; Yingyao Wang; Yan Li; Xiaoping Lin; Zhen Hong; Jiapeng Huang; Xuanrui Zhang; Yuexin Yang; Yixiang Su (Critical Reviews in Food Science and Nutrition, 2023)

Effects of light regimes and benthic fish disturbance on the foraging behavior of Vallisneria natans in heterogeneous sediments - Hong Su; Mingfan Li; Chao Wang; Guanbao Fu; Ruijie Le; Gang Sun (Environmental Science and Pollution Research, 2023)

Monoterpenoids from the root bark of Acanthopanax gracilistylus and their inhibitory effects on neutrophil elastase, 5-lipoxygenase, andcyclooxygenase-2 in vitro - Hao-Dong Yang; Zhi-Shu Tang; Tao-Tao Xue; Huai-Li Xu; Bao-Long Hou; Ya-Ya Zhu; Zeng-Hu Su; Hong-Bo Xu (Phytochemistry, 2023)

Daytime and nighttime high temperatures differentially increased the risk of cardiovascular disease: A nationwide hospital-based study in China - Junwen Tao; Yongming Zhang; Zhiwei Li; Min Yang; Cunrui Huang; Mohammad Zahid Hossain; Yuanyong Xu; Xianyu Wei; Hong Su; Jian Cheng; Wenyi Zhang (Environmental Research, 2023)

HVT-vectored H7 vaccine protects chickens from lethal infection with the highly pathogenic H7N9 Avian inﬂuenza virus - Yi-qun Chen; Guan-ming Su; Jia-hao Zhang; Bo Li; Kai-xiong Ma; Xu Zhang; Li-hong Huang; Ming Liao; Wen-bao Qi (Veterinary Microbiology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Surface imprinted-covalent organic frameworks for efficient solid-phase extraction of fluoroquinolones in food samples - Li-Hong Su; Hai-Long Qian; Cheng Yang; Chuanxi Wang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Macrocyclic lactone residues in cattle dung result in a sharp decline in the population of dung beetles in the rangelands of northern China - Hua Su; Hong Xu; Benying Su; Wei Liu; Yingfei Cao; Yonggeng Li (Agriculture, Ecosystems & Environment, 2023)

Effects of salinity on methane emissions and methanogenic archaeal communities in different habitat of saline-alkali wetlands - Feng Li; Huiju Li; Huihui Su; Wei Du; Zhongyan Gao; Huajun Liu; Hong Liang; Dawen Gao (Environmental Science and Pollution Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Corrigendum to “Maternal linuron exposure alters testicular development in male offspring rats at the whole genome level” [Toxicology 389 (2017) 13–20] - Jianwei Bai; Hua Han; Feng Wang; Liyu Su; Hongwei Ding; Xiyin Hu; Binli Hu; Hong Li; Wei Zheng; Yan Li (Toxicology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

The association between greenery type and gut microbiome in schizophrenia: did all greenspaces play the equivalent role? - Ning Wei; Shusi Wang; Xuanxuan Li; Rubing Pan; Weizhuo Yi; Jian Song; Li Liu; Jintao Liu; Jiajun Yuan; Rong Song; Jian Cheng; Hong Su (Environmental Science and Pollution Research, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Prediction of pyrolysis product yield of medical waste based on BP neural network - Yangwei Wu; Aijun Li; Su Lei; Tong Zhang; Qian Deng; Haoyu Tang; Hong Yao (Process Safety and Environmental Protection, 2023)

Sustainable production of flocculant-containing bacterial cellulose composite for removal of PET nano-plastics - Hong Lu; Su Sun; Jidan Sun; Xiongyi Peng; Ning Li; Muhammad Wajid Ullah; Yanbo Zhang; Li Chen; Jiangang Zhou (Chemical Engineering Journal, 2023)

Indoor air quality and its health effects in offices and school buildings in the Yangtze River Delta - Chanjuan Sun; Jingyu Chen; Shijie Hong; Yinping Zhang; Haidong Kan; Zhuohui Zhao; Furong Deng; Xiangang Zeng; Yuexia Sun; Hua Qian; Wei Liu; Jinhan Mo; et al. (Air Quality, Atmosphere & Health, 2023)

Ocellatuspyrones A‒G, new antibacterial polypropionates from the Chinese mollusk Placobranchus ocellatus - Song-Wei Li; Dan-Dan Yu; Ming-Zhi Su; Li-Gong Yao; Hong Wang; Xueting Liu; Yue-Wei Guo (Marine Life Science & Technology, 2023)
Marine invertebrates serve as rich sources of secondary metabolites with intriguing chemical diversities and a wide spectrum of biological activities. Particularly, marine shell-less sacoglossan mollusks have attracted much attentions due to the fact that mollusks apply complex metabolites as chemical defense agents against to their predators. With the purpose of discovering bioactive secondary metabolites to develop marine-derived medicines from the South China Sea, we have conducted a chemical study on the photosynthetic mollusk Placobranchus ocellatus. As a result, seven new γ -pyrone polypropionates, namely ( ±)-ocellatuspyrone A ( 1 ), ( ±)-ocellatuspyrone B ( 2 ), and ocellatuspyrones C−G ( 5 , 9 − 12 ), along with five known polypropionates, have been isolated and characterized from the South China Sea photosynthetic mollusk Placobranchus ocellatus . Extensive spectroscopic analysis, single crystal X-ray diffraction analysis, modified Mosher’s method, ECD comparison, CD exciton chirality method, TDDFT-ECD calculation, and chemical conversion were used to determine the structures and absolute configurations of the new compounds and the stereochemistry of undefined known compounds 4 , 6 and 7 . All these isolated polypropionates were evaluated in bioassays for their biological activities, including antibacterial, neuroprotective effect, anti-inflammatory, PTP1B inhibitory, and antiviral activities. Compounds 7 , 8 and 11 were found for the first time to show antibacterial activity against fish pathogenic bacteria Streptococcus parauberis (the main pathogen causing fish streptococcal infections and acute death) with MIC values of 35.8, 34.2, and 37.4 μg/mL, respectively, which might be potential novel antibacterial agents for the treatment of fish infectious diseases.

The ratio of monocyte count and high-density lipoprotein cholesterol mediates the association between urinary tungsten and cardiovascular disease: a study from NHANES 2005–2018 - Yudong Wu; Yajie Meng; Weizhuo Yi; Rubing Pan; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Jian Song; Shasha Song; et al. (Environmental Science and Pollution Research, 2023)

The deficiency of N6-methyladenosine demethylase ALKBH5 enhances the neurodegenerative damage induced by cobalt - Chunyan Zheng; Guangxia Yu; Qianqian Su; Lingyan Wu; Jianping Tang; Xinpei Lin; Yao Chen; Zhenkun Guo; Fuli Zheng; Hong Zheng; Liqiong Lin; Ying Tang; et al. (Science of The Total Environment, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

Rapid increase in tropospheric ozone over Southeast Asia attributed to changes in precursor emission source regions and sectors - Su Li; Yang Yang; Hailong Wang; Pengwei Li; Ke Li; Lili Ren; Pinya Wang; Baojie Li; Yuhao Mao; Hong Liao (Atmospheric Environment, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Identification of 14 glutathione S-transferase genes from Lasioderma serricorne and characterization of LsGSTe1 involved in lambda-cyhalothrin detoxification - Xi-Ya Liu; Hui-Mei Sun; Yi-Hong Luo; Mao-Ye Li; Hai-Bing Liu; Su Liu (Pesticide Biochemistry and Physiology, 2023)

Built environment and schizophrenia re-hospitalization risk in China: A cohort study - Jian Song; Yunfeng Liang; Zhiwei Xu; Yudong Wu; Shuangshuang Yan; Lu Mei; Xiaoni Sun; Yuxuan Li; Xiaoyu Jin; Weizhuo Yi; Rubing Pan; Jian Cheng; et al. (Environmental Research, 2023)

Identification and validation of new MADS-box homologous genes in 3010 rice pan-genome - Weihua Li; Duoxiang Wang; Xiaokun Hong; Jin Shi; Jun Hong; Su Su; Cristopher Reyes Loaiciga; Jing Li; Wanqi Liang; Jianxin Shi; Dabing Zhang (Plant Cell Reports, 2023)

Carp stocking and climate change are potentially more important factors than nutrient enrichment driving water quality deterioration in subtropical freshwater lakes in China - Haojie Su; Jianfeng Chen; Yun Li; Qingyang Rao; Congqiang Luo; Xuwei Deng; Hong Shen; Renhui Li; Jun Chen; Yuanfeng Sun; Jiamin Pan; Suhui Ma; et al. (Limnology and Oceanography, 2023)
Freshwater lakes across the world have undergone dramatic changes in biological components and water quality over the past several decades. Previous studies focused on potential drivers mainly on nutrient enrichment in the catchment. However, the relative importance of climate change and the top‐down cascade effects of fish stocking on water quality is not fully understood. Here, by compiling 155 lakes data with four periods of field investigation in subtropical lakes in China, we found no significant changes in water total nitrogen and total phosphorus in the past two decades. However, the phytoplankton abundance increased significantly, and the water clarity declined by 44.1%. We further found that carp stocking and climate change are potentially more important than nutrients driving water quality change, which is also evidenced in two lakes (Lake Donghu and Qiandao) with long‐term monitoring histories. Specifically, carp stocking can decrease the water clarity directly by stirring up sediment and indirectly by trophic cascade along the food web. For climatic factors, mean annual temperature (MAT) has a positive effect on phytoplankton abundance, while mean annual precipitation has a negative one, with climates overall having little effect on water clarity. In addition, nutrient enrichment and climate change also have strong interactions with carp stocking, which may enhance the top‐down effects on water quality. Our findings highlight that either MAT or carp stocking may become an overwhelming driver of water clarity decline, which provides new insights into the conservation strategy for water quality management in the subtropical lakes in China.

Effects of benthic fish and light regimes on water quality and the growth of Vallisneria natans with two sediment types - Hong Su; Wenhui Zheng; Mingfan Li; Chao Wang; Guanbao Fu; Ruijie Le; Gang Sun (Environmental Science and Pollution Research, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Fluvial entrenchment of the Gonghe Basin and integration of the upper Yellow River - Evidence from the cosmogenically dated geomorphic surfaces - Qi Su; Xianyan Wang; Daoyang Yuan; Hong Xie; Hongxuan Li; Xilei Huang (Geomorphology, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Associations of polycyclic aromatic hydrocarbons, water-soluble ions and metals in PM2.5 with liver function: Evidence from schizophrenia cohort - Weizhuo Yi; Jun Cheng; Jian Song; Rubing Pan; Yunfeng Liang; Xiaoni Sun; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Xiaoyu Jin; Lu Mei; Jian Cheng; et al. (Science of The Total Environment, 2023)

Triclocarban triggers osteoarthritis via DNMT1-mediated epigenetic modification and suppression of COL2A in cartilage tissues - Yibo Zhang; Liu He; Yiqi Yang; Jieqiong Cao; Zijian Su; Bihui Zhang; Huiying Guo; Zhenyu Wang; Peiguang Zhang; Junye Xie; Jieruo Li; Jinshao Ye; et al. (Journal of Hazardous Materials, 2023)

Optimizing safe and just operating spaces at sub-watershed scales to guide local environmental management - Yanyu Su; Xuhui Dong; Yan Li; Quan Hong; Roger Flower (Journal of Cleaner Production, 2023)

Purification and biochemical characterization of a novel ene- reductase from Kazachstania exigua HSC6 for dihydro-β-ionone from β-ionone - Zhangde Long; Kena Li; Yun Xue; Yongwei Sun; Jigang Li; Zan Su; Jiansheng Sun; Qibin Liu; Hong Liu; Tao Wei (Biotechnology Letters, 2023)

Polyketides with potential bioactivities from the mangrove-derived fungus Talaromyces sp. WHUF0362 - Huawei Lv; Haibo Su; Yaxin Xue; Jia Jia; Hongkai Bi; Shoubao Wang; Jinkun Zhang; Mengdi Zhu; Mahmoud Emam; Hong Wang; Kui Hong; Xing-Nuo Li (Marine Life Science & Technology, 2023)
Metabolites of microorganisms have long been considered as potential sources for drug discovery. In this study, five new depsidone derivatives, talaronins A-E ( 1–5 ) and three new xanthone derivatives, talaronins F–H ( 6–8 ), together with 16 known compounds ( 9–24 ), were isolated from the ethyl acetate extract of the mangrove-derived fungus Talaromyces species WHUF0362. The structures were elucidated by analysis of spectroscopic data and chemical methods including alkaline hydrolysis and Mosher’s method. Compounds 1 and 2 each attached a dimethyl acetal group at the aromatic ring. A putative biogenetic relationship of the isolated metabolites was presented and suggested that the depsidones and the xanthones probably had the same biosynthetic precursors such as chrysophanol or rheochrysidin. The antimicrobial activity assay indicated that compounds 5 , 9 , 10 , and 14 showed potent activity against Helicobacter pylori with minimum inhibitory concentration (MIC) values in the range of 2.42–36.04 μmol/L. While secalonic acid D ( 19 ) demonstrated significant antimicrobial activity against four strains of H. pylori with MIC values in the range of 0.20 to 1.57 μmol/L. Furthermore, secalonic acid D ( 19 ) exhibited cytotoxicity against cancer cell lines Bel-7402 and HCT-116 with IC 50 values of 0.15 and 0.19 μmol/L, respectively. The structure–activity relationship of depsidone derivatives revealed that the presence of the lactone ring and the hydroxyl at C-10 was crucial to the antimicrobial activity against H. pylori . The depsidone derivatives are promising leads to inhibit H. pylori and provide an avenue for further development of novel antibiotics.

Transformation of hydroxylamine to nitrosated and nitrated products during advanced oxidation process - Zi-jun Dong; Cheng-chun Jiang; Yue Zhou; Jie-bin Duan; Li-hong Wang; Su-yan Pang; Jin Jiang; Xiao-hui Sun (Journal of Hazardous Materials, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Water level of inland saline wetlands with implications for CO2 and CH4 fluxes during the autumn freeze–thaw period in Northeast China - Weijie Wang; Hong Liang; Feng Li; Huihui Su; Huiju Li; Dawen Gao (Environmental Science and Pollution Research, 2023)

Identification and pathogenetic study of tilapia lake virus (TiLV) isolated from naturally diseased tilapia - Tao He; Yu-Zhou Zhang; Li-Hong Gao; Bo Miao; Ji-Shu Zheng; De-Cheng Pu; Qing-Qing Zhang; Wei-Wei Zeng; De-Shou Wang; Sheng-Qi Su; Song Zhu (Aquaculture, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Association of outdoor air pollution, lifestyle, genetic factors with the risk of lung cancer: A prospective cohort study - Huaying Liang; Xin Zhou; Yiqun Zhu; Dianwu Li; Danrong Jing; Xiaoli Su; Pinhua Pan; Hong Liu; Yan Zhang (Environmental Research, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

Mechano-responsive microRNA-functionalized PDLSC exosomes as a novel therapeutic for inflammatory bone loss in periodontitis - Rui Wang; Li Liao; Xiaojun Huang; Shixing Ma; Shuang Wang; Hu Qiao; Hong Zhou; Jing Zou; Xiaoxia Su (Chemical Engineering Journal, 2023)

Phenotypic aging mediates the association between blood cadmium and depression: a population-based study - Yudong Wu; Qing Wu; Rubing Pan; Weizhuo Yi; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Lu Mei; Shuangshuang Yan; Xiaoni Sun; Wei Qin; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

This is what we know: Assessing the stock status of the data-poor skipjack tuna (Katsuwonus pelamis) fishery in the South China Sea - Kui Zhang; Jun Zhang; Peng Zhang; Li Su; Xiaofan Hong; Yongsong Qiu; Zuozhi Chen (Frontiers in Marine Science, 2023)
Skipjack tuna ( Katsuwonus pelamis ) is a highly migratory species of significant value in global marine fisheries. The South China Sea (SCS) is the largest marginal sea in the northwestern Pacific Ocean, and many tuna and tuna-like species occur within it. Although a recent Western and Central Pacific Fisheries Commission report identified skipjack tuna in the western and central Pacific to be sustainably fished, the exploitation status of skipjack tuna in the SCS is still unclear, due to limited data. We apply two data-poor methods, length-based Bayesian biomass estimation (LBB) and length-based spawning potential ratio (LBSPR), to assess the status of skipjack tuna stock in the SCS. We use electronic length frequency analysis to estimate von Bertalanffy growth parameters (asymptotic length L inf and growth coefficient K ) to serve as priors for LBB and LBSPR estimation. Estimates are calculated for SCS skipjack tuna L inf (68.3 cm), K (0.325 year −1 ), natural mortality (0.49 year −1 ) and mean fork length at 50% sexual maturity (36.7 cm). LBB analysis reveals the estimated relative stock size (0.29) indicates that the SCS skipjack tuna stock maybe heavily overfished. LBSPR analysis reveals the estimated spawning potential ratio for this fishery to be 3%, which is significantly below the limit reference point of 20%. Accordingly, for the SCS skipjack tuna stock we identify a need to reduce fishing mortality by controlling fishing effort and increasing catchable size.

CircMAN1A2 contributes to nasopharyngeal carcinoma progression via enhancing the ubiquitination of ATMIN through miR-135a-3p/UBR5 axis - Qian-Qian Dang; Pei-Hong Li; Juan Wang; Jing-Yi Zhao; Su-Nan Zhai; Ying-Juan Zheng; Dao-Ke Yang (Human Cell, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Effects of urban particulate matter on gut microbiome and partial schizophrenia-like symptoms in mice: Evidence from shotgun metagenomic and metabolomic profiling - Weizhuo Yi; Yifu Ji; Hua Gao; Shengyong Luo; Rubing Pan; Jian Song; Yangyang He; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Yunfeng Liang; Xiaoni Sun; et al. (Science of The Total Environment, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Efficient caproate production from ethanol and acetate in open culture system through reinforcement of chain elongation process - Cunsheng Zhang; Zhihui Ling; Li Yang; Yan Liu; Tianyu Cao; Yuxuan Sun; Weimin Liu; Shuhao Huo; Zhi-Hong Zhang; Haijia Su; Jan Baeyens; Xianghui Qi (Journal of Cleaner Production, 2023)

Ir nanodots decorated Ni3Fe nanoparticles for boosting electrocatalytic water splitting - Yaru Li; Yong-Chen Miao; Chen Yang; Yu-Xin Chang; Yu Su; Hong Yan; Sailong Xu (Chemical Engineering Journal, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Evidence in Support of Analogical Reasoning Improvements with Executive Attention Intervention in Healthy Young Adults - Yixuan Lin; Qing Li; Mengke Zhang; Yujie Su; Xiangpeng Wang; Hong Li; Antao Chen (Neuroscience Bulletin, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Classification of primary dysmenorrhea by brain effective connectivity of the amygdala: a machine learning study - Siyi Yu; Liying Liu; Ling Chen; Menghua Su; Zhifu Shen; Lu Yang; Aijia Li; Wei Wei; Xiaoli Guo; Xiaojuan Hong; Jie Yang (Brain Imaging and Behavior, 2022)

Is higher ambient temperature associated with acute appendicitis hospitalizations? A case-crossover study in Tongling, China - Yuxuan Li; Xuelian Luo; Yudong Wu; Shuangshuang Yan; Yunfeng Liang; Xiaoyu Jin; Xiaoni Sun; Lu Mei; Chao Tang; Xiangguo Liu; Yangyang He; Weizhuo Yi; et al. (International Journal of Biometeorology, 2022)

Genetic basis underlying tiller angle in rice (Oryza sativa L.) by genome-wide association study - Shaoxing Bai; Jun Hong; Su Su; Zhikang Li; Wensheng Wang; Jianxin Shi; Wanqi Liang; Dabing Zhang (Plant Cell Reports, 2022)

Retraction Note: Stabilization of the histone acetyltransferase Tip60 by deubiquitinating enzyme USP7 stimulates the release of pro-inflammatory mediators in acute lung injury - Jing Wang; Hong-Yan Li; Zhen-Bo Su (Journal of Molecular Medicine, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Characterization, heterologous expression and engineering of trehalase for biotechnological applications - Han Gao; Jin-Song Gong; Chang Su; Heng Li; Zheng-Hong Xu; Jin-Song Shi (Systems Microbiology and Biomanufacturing, 2022)

Comprehensive analysis using multiple-integrated techniques on the failure mechanism and dynamic process of a long run-out landslide: Jichang landslide case - Yiding Bao; Hong Wang; Lijun Su; Dajiang Geng; Liang Yang; Peng Shao; Yuchao Li; Ni Du (Natural Hazards, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Qipengyuania thermophila sp. nov., isolated from a Chinese hot spring - Zi-Yu Zhao; Ting-Ting Xia; Jian-Yu Jiao; Lan Liu; Qing-Yang Su; Meng-Meng Li; Ai-Ping Lv; Yu-Ting Ouyang; Wen-Jun Li; Hong Ming (Archives of Microbiology, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Effects of extreme precipitation on hospitalization risk and disease burden of schizophrenia in urban and rural Lu’an, China, from 2010 to 2019 - Yudong Wu; Zhenghai Yao; Gongyan Ma; Jian Cheng; Huabin Xu; Wei Qin; Weizhuo Yi; Rubing Pan; Qiannan Wei; Chao Tang; Xiangguo Liu; Yangyang He; et al. (Environmental Science and Pollution Research, 2022)

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

Stereumamides E-H, four new minor quaternary ammonium hybrids from Stereum hirsutum - Qian-Yi Hu; Yuan-Chang Duan; Xue-Juan Pu; Su-Su Li; Guo-Hong Li; Pei-Ji Zhao (Natural Product Research, 2022)

Deep learning model based on big data for water source discrimination in an underground multiaquifer coal mine - Chunlu Jiang; Saijun Zhu; Hong Hu; Shikai An; Wei Su; Xing Chen; Chang Li; Liugen Zheng (Bulletin of Engineering Geology and the Environment, 2022)

Species diversity in Penicillium and Acaulium from herbivore dung in China, and description of Acaulium stercorarius sp. nov - Lei Su; Hua Zhu; Peilin Sun; Xue Li; Bochao Yang; Hong Gao; Zhiguang Xiang; Chuan Qin (Mycological Progress, 2021)

Hyper-SUMOylation of SMN induced by SENP2 deficiency decreases its stability and leads to spinal muscular atrophy-like pathology - Yuhong Zhang; Xu Chen; Qiqi Wang; Congcong Du; Wenbin Lu; Hong Yuan; Zhenzhen Zhang; Danqing Li; Xing Ling; Xiang Ren; Yang Zhao; Qi Su; et al. (Journal of Molecular Medicine, 2021)

Characterization of the novel hybrid cultivar E25 of Saccharina japonica in the northern farming region of China - Li Su; Ti Feng Shan; Jing Li; Su Qin Gao; Shao Jun Pang; Xiao Fei Leng; Yan Zhang; Ming Fu Zhang; Hong Tao Gao (Journal of Applied Phycology, 2021)

The first description of alate and supplementary description of soldier of Reticulitermes aculabialis Tsai et Hwang (Isoptera, Rhinotermitidae) - Zahid Khan; Yu-Xin Li; Qing Liu; Xiao-Hong Su; Lian-Xi Xing (International Journal of Tropical Insect Science, 2021)

Effects of different heat exposure patterns (accumulated and transient) and schizophrenia hospitalizations: a time-series analysis on hourly temperature basis - Chao Tang; Yifu Ji; Qingru Li; Zhenhai Yao; Jian Cheng; Yangyang He; Xiangguo Liu; Rubing Pan; Qiannan Wei; Weizhuo Yi; Hong Su (Environmental Science and Pollution Research, 2021)

A novel thermophilic β-carotene 15,15′-monooxygenase with broad substrate specificity from the marine bacterium Candidatus Pelagibacter sp. HTCC7211 - Zhangde Long; Yuzhe Zhao; Yun Xue; Min Wang; Jigang Li; Zan Su; Jiansheng Sun; Qibin Liu; Hong Liu; Duobin Mao; Tao Wei (Biotechnology Letters, 2021)

Inhibition of Maternal c-Src Ameliorates the Male Offspring Hypertension by Suppressing Inflammation and Neurotransmitters in the Paraventricular Nucleus - Qing Su; Xiao-Jing Yu; Qing Yang; Xiao-Min Wang; Wen-Jie Xia; Hong-Bao Li; Kai-Li Liu; Qiu-Yue Yi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Experimental study of displacement field of layered soils surrounding laterally loaded pile based on transparent soil - Bingxiang Yuan; Zihao Li; Zuqing Zhao; Hong Ni; Zhilei Su; Zhijie Li (Journal of Soils and Sediments, 2021)

RNA-Seq Transcriptome Analysis of the Liver and Brain of the Black Carp (Mylopharyngodon piceus) During Fasting - Ya-Fan Dai; Yu-bang Shen; Shen-Tong Wang; Jia-Hua Zhang; Yu-Hong Su; Sheng-Chen Bao; Xiao-Yan Xu; Jia-Le Li (Marine Biotechnology, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

Exogenous ABA and its inhibitor regulate flower bud induction of apple cv. ‘Nagafu No. 2′ grafted on different rootstocks - Wen-Fang Li; Juan Mao; Jing Su; Xin-Wen Li; Mohammed Mujitaba Dawuda; Zong-Huan Ma; Cun-Wu Zuo; Ze-Shan An; Bai-Hong Chen (Trees, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Bing Liu; Jiao Qiao; Jinxiu Hu; Minghua Fan; Yanfang Zhao; Hong Su; Ziyang Wang; Qun Yu; Qiqi Ma; Yanmei Li; Zhimei Lv; Rong Wang (Molecular and Cellular Biochemistry, 2020)

Direct and indirect plant defenses induced by (Z)-3-hexenol in tomato against whitefly attack - Fengbo Yang; Qinghe Zhang; Qixi Yao; Gong Chen; Hong Tong; Jianmin Zhang; Chuanren Li; Qi Su; Youjun Zhang (Journal of Pest Science, 2020)

Directional seismic response to the complex topography: A case study of 2013 Lushan Ms 7.0 earthquake - Bo Zhao; Yun-sheng Wang; Li-jun Su; Yong-hong Luo; Jing Zhang (Journal of Mountain Science, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

TMEM88 modulates the secretion of inflammatory factors by regulating YAP signaling pathway in alcoholic liver disease - Liang-yun Li; Chen-chen Yang; Su-wen Li; Yu-min Liu; Hao-dong Li; Shuang Hu; Hong Zhou; Jin-liang Wang; Hang Shen; Xiao-ming Meng; Jun Li; Tao Xu (Inflammation Research, 2020)

RETRACTED ARTICLE: Stabilization of the histone acetyltransferase Tip60 by deubiquitinating enzyme USP7 stimulates the release of pro-inflammatory mediators in acute lung injury - Jing Wang; Hong-Yan Li; Zhen-Bo Su (Journal of Molecular Medicine, 2020)

The association between prenatal endocrine-disrupting chemical exposure and altered resting-state brain fMRI in teenagers - Jun-Cheng Weng; Chi Ieong Hong; Jeng-Dau Tasi; Chao-Yu Shen; Pen-Hua Su; Shu-Li Wang (Brain Structure and Function, 2020)

Improved production of GTKO/hCD55/hCD59 triple-gene-modified Diannan miniature pigs for xenotransplantation by recloning - Heng Zhao; Yuying Li; Thanapa Wiriyahdamrong; Zaimei Yuan; Yubo Qing; Honghui Li; Kaixiang Xu; Jianxiong Guo; Baoyu Jia; Xuezeng Zhang; Wenmin Cheng; Yanhua Su; et al. (Transgenic Research, 2020)

A DTW distance-based seismic waveform clustering method for layers of varying thickness - Zhong Hong; Kun-Hong Li; Ming-Jun Su; Guang-Min Hu; Jun Yang; Gai Gao; Bin Hao (Applied Geophysics, 2020)

Leaf size of woody dicots predicts ecosystem primary productivity - Yaoqi Li; Peter B. Reich; Bernhard Schmid; Nawal Shrestha; Xiao Feng; Tong Lyu; Brian S. Maitner; Xiaoting Xu; Yichao Li; Dongting Zou; Zheng‐Hong Tan; Xiangyan Su; et al. (Ecology Letters, 2020)
A key challenge in ecology is to understand the relationships between organismal traits and ecosystem processes. Here, with a novel dataset of leaf length and width for 10 480 woody dicots in China and 2374 in North America, we show that the variation in community mean leaf size is highly correlated with the variation in climate and ecosystem primary productivity, independent of plant life form. These relationships likely reflect how natural selection modifies leaf size across varying climates in conjunction with how climate influences canopy total leaf area. We find that the leaf size‒primary productivity functions based on the Chinese dataset can predict productivity in North America and vice‐versa. In addition to advancing understanding of the relationship between a climate‐driven trait and ecosystem functioning, our findings suggest that leaf size can also be a promising tool in palaeoecology for scaling from fossil leaves to palaeo‐primary productivity of woody ecosystems.

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Blockade of c-Src Within the Paraventricular Nucleus Attenuates Inflammatory Cytokines and Oxidative Stress in the Mechanism of the TLR4 Signal Pathway in Salt-Induced Hypertension - Qing Yang; Xiao-Jing Yu; Qing Su; Qiu-Yue Yi; Xin-Ai Song; Xiao-Lian Shi; Hong-Bao Li; Jie Qi; Guo-Qing Zhu; Yu-Ming Kang (Neuroscience Bulletin, 2020)

Brain structural basis of individual variability in dream recall frequency - Shuqin Zhou; Jing Xu; Zihui Su; Yuezhen Li; Yan Shao; Hongqiang Sun; Huaiqiu Zhu; Qihong Zou; Jia-Hong Gao (Brain Imaging and Behavior, 2019)

Using two contrasting methods with the same tracers to trace the main sediment source in a mountainous catchment - Han Wu; Dong-hong Xiong; Su Zhang; Yong Yuan; Wan-Xin Li; Lin Liu; Zheng-an Su; Xiao-ning Lu (Journal of Mountain Science, 2019)

Antihyperlipidemic glycosides from the root bark of Lycium chinense - Hui Chen; Yu-Jie Li; Yan-Jun Sun; Xiao-Kun Li; Gong Jian-Hong; Ya Wu; Fang-Yi Su; Kun Du; Yan-Li Zhang; Wei-Sheng Feng (Natural Product Research, 2019)

Effects of CEPA and 1-MCP on Flower Bud Differentiation of Apple cv. ‘Nagafu No.2’ Grafted on Different Rootstocks - Wen-Fang Li; Juan Mao; Xin-Wen Li; Jing Su; Mohammed Mujitaba Dawuda; Zong-Huan Ma; Cun-Wu Zuo; Ze-Shan An; Bai-Hong Chen (Journal of Plant Growth Regulation, 2019)

Recent research progress in geochemical properties and restoration of heavy metals in contaminated soil by phytoremediation - Jiang-tao Fu; Dong-mei Yu; Xi Chen; Ying Su; Cai-hong Li; Yong-ping Wei (Journal of Mountain Science, 2019)

Correction to: Antidepressant-Like Action of Single Facial Injection of Botulinum Neurotoxin A is Associated with Augmented 5-HT Levels and BDNF/ERK/CREB Pathways in Mouse Brain - Yang Li; Jing Liu; Xu Liu; Cun-Jin Su; Qi-Lin Zhang; Zhi-Hong Wang; Lei-Fang Cao; Xue-Yan Guo; Ya Huang; Weifeng Luo; Tong Liu (Neuroscience Bulletin, 2019)

Antidepressant-Like Action of Single Facial Injection of Botulinum Neurotoxin A is Associated with Augmented 5-HT Levels and BDNF/ERK/CREB Pathways in Mouse Brain - Yang Li; Jing Liu; Xu Liu; Cun-Jin Su; Qi-Lin Zhang; Zhi-Hong Wang; Lei-Fang Cao; Xue-Yan Guo; Ya Huang; Weifeng Luo; Tong Liu (Neuroscience Bulletin, 2019)

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Formation, extracellular polymeric substances, and structural stability of aerobic granules enhanced by granular activated carbon - Zixuan Liang; Qianqian Tu; Xiaoxuan Su; Xiangyu Yang; Junyu Chen; Yi Chen; Hong Li; Caihong Liu; Qiang He (Environmental Science and Pollution Research, 2019)

Effects of different green manure treatments on soil apparent N and P balance under a 34-year double-rice cropping system - Xi Hong; Chao Ma; Jusheng Gao; Shiming Su; Tao Li; Zunchang Luo; Ran Duan; Yanan Wang; Lingyu Bai; Xibai Zeng (Journal of Soils and Sediments, 2019)

Alterations in the Neurobehavioral Phenotype and ZnT3/CB-D28k Expression in the Cerebral Cortex Following Lithium-Pilocarpine-Induced Status Epilepticus: the Ameliorative Effect of Leptin - Hong Ni; Su-hong Chen; Li-li Li; Mei-fang Jin (Biological Trace Element Research, 2019)

Selective Inhibition on Organic Cation Transporters by Carvedilol Protects Mice from Cisplatin-Induced Nephrotoxicity - Dong Guo; Hong Yang; Qing Li; Hyo Jung Bae; Obinna Obianom; Sujuan Zeng; Tong Su; James E. Polli; Yan Shu (Pharmaceutical Research, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Assessing a scheme of spatial-temporal thermal remote-sensing sharpening for estimating regional evapotranspiration - Kai Liu; Hongbo Su; Jing Tian; Xueke Li; Weimin Wang; Lijun Yang; Hong Liang (International Journal of Remote Sensing, 2018)

Morphology and multigene phylogeny reveal new genus and species of Torulaceae from freshwater habitats in northwestern Yunnan, China - Xi-Jun Su; Zong-Long Luo; Rajesh Jeewon; Darbhe J. Bhat; Dan-Feng Bao; Wen-Li Li; Yu-E Hao; Hong-Yan Su; Kevin D. Hyde (Mycological Progress, 2018)

Morphological and molecular taxonomy of novel species Pleurotheciaceae from freshwater habitats in Yunnan, China - Zong-Long Luo; Kevin D. Hyde; Darbhe J. Bhat; Rajesh Jeewon; Sajeewa S. N. Maharachchikumbura; Dan-Feng Bao; Wen-Li Li; Xi-Jun Su; Xiao-Yan Yang; Hong-Yan Su (Mycological Progress, 2018)

Moss habitats distinctly affect their associated bacterial community structures as revealed by the high-throughput sequencing method - Su Wang; Jing Yan Tang; Jing Ma; Xue Dong Li; Yan Hong Li (World Journal of Microbiology and Biotechnology, 2018)

Roles of Nitric Oxide Synthase Isoforms in Neurogenesis - Cheong-Meng Chong; Nana Ai; Minjing Ke; Yuan Tan; Zhijian Huang; Yong Li; Jia-Hong Lu; Wei Ge; Huanxing Su (Molecular Neurobiology, 2018)

Retraction Note to: miR-124 Acts as a Tumor Suppressor in Glioblastoma via the Inhibition of Signal Transducer and Activator of Transcription 3 - Weihao Li; Hui Huang; Junhua Su; Xin Ji; Xiaobin Zhang; Zhiping Zhang; Hong Wang (Molecular Neurobiology, 2017)

Erratum to: Characteristics and triggering mechanism of Xinmo landslide on 24 June 2017 in Sichuan, China - Li-jun Su; Kai-heng Hu; Wei-feng Zhang; Jiao Wang; Yu Lei; Chong-lei Zhang; Peng Cui; Alessandro Pasuto; Quan-hong Zheng (Journal of Mountain Science, 2017)

Oxidative stress promotes myocardial fibrosis by upregulating KCa3.1 channel expression in AGT-REN double transgenic hypertensive mice - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2017)

Characteristics and triggering mechanism of Xinmo landslide on 24 June 2017 in Sichuan, China - Li-jun Su; Kai-heng Hu; Wei-feng Zhang; Jiao Wang; Yu Lei; Chong-lei Zhang; Peng Cui; Alessandro Pasuto; Quan-hong Zheng (Journal of Mountain Science, 2017)

Integrated analysis of leaf morphological and color traits in different populations of Chinese cabbage (Brassica rapa ssp. pekinensis) - Su Ryun Choi; Xiaona Yu; Vignesh Dhandapani; Xiaonan Li; Zhi Wang; Seo Yeon Lee; Sang Heon Oh; Wenxing Pang; Nirala Ramchiary; Chang Pyo Hong; Suhyoung Park; Zhongyun Piao; et al. (Theoretical and Applied Genetics, 2017)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

Analysis on shear wave velocity structure of a gravel landslide based on dual-source surface wave method - Xing-qian Xu; Li-jun Su; Guang-da Zhang; Hong-hu Zhu (Landslides, 2017)

Warm–cold colonization: response of oaks to uplift of the Himalaya–Hengduan Mountains - Hong‐Hu Meng; Tao Su; Xiao‐Yang Gao; Jie Li; Xiao‐Long Jiang; Hang Sun; Zhe‐Kun Zhou (Molecular Ecology, 2017)
Clarifying the relationship between distribution patterns of organisms and geological events is critical to understanding the impact of environmental changes on organismal evolution. Quercus sect. Heterobalanus is now distributed across the Himalaya–Hengduan Mountains ( HHM ) and warm lowland in East China, yet how the distribution patterns of this group changed in response to the HHM uplift remains largely unknown. This study examines the effect of tectonic events in the HHM region on the oaks, providing a biological perspective on the geological history of this region. Fifty‐six populations of Quercus sect. Heterobalanus were genotyped using four chloroplast DNA regions and nine nuclear simple sequence repeat loci to assess population structure and diversity, supplemented by molecular dating and ancestral area reconstructions. The underlying demographic dynamics were compared using ecological niche models of the species distributions during the last glacial maximum and the present. These analyses illustrate that Quercus sect. Heterobalanus diversified as the HHM uplifted and climatic cooling during the mid‐Miocene, colonizing the cold habitats from warm broadleaf mixed forests. Lineages in cold highlands and warm lowlands have diverged as a consequence of local adaptation to diverging climates since the late Miocene. Our results suggest that continuous uplift of the HHM in the late Miocene to early Pliocene accompanied by simultaneous cooling triggered the differentiation of oaks. The biogeography of Quercus sect. Heterobalanus illuminates the geological events responsible for the modern‐day HHM .

RETRACTED ARTICLE: miR-124 Acts as a Tumor Suppressor in Glioblastoma via the Inhibition of Signal Transducer and Activator of Transcription 3 - Weihao Li; Hui Huang; Junhua Su; Xin Ji; Xiaobin Zhang; Zhiping Zhang; Hong Wang (Molecular Neurobiology, 2017)

Impact of short-term temperature variability on emergency hospital admissions for schizophrenia stratified by season of birth - Desheng Zhao; Xulai Zhang; Zhiwei Xu; Jian Cheng; Mingyu Xie; Heng Zhang; Shusi Wang; Kesheng Li; Huihui Yang; Liying Wen; Xu Wang; Hong Su (International Journal of Biometeorology, 2017)

Impact of weather factors on hand, foot and mouth disease, and its role in short-term incidence trend forecast in Huainan City, Anhui Province - Desheng Zhao; Lulu Wang; Jian Cheng; Jun Xu; Zhiwei Xu; Mingyu Xie; Huihui Yang; Kesheng Li; Lingying Wen; Xu Wang; Heng Zhang; Shusi Wang; et al. (International Journal of Biometeorology, 2017)

Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities - Shuang-Xi Mei; Xu-Hong Li; Li-Guo Yang; Xiao-Hui Li; Jia-Ying Xie; Qi Yao; Mei Su; Tao Cui; Jing-Kun Wang; Zhao-Yun Zhu (Natural Product Research, 2017)

Impacts of temperature change on ambulance dispatches and seasonal effect modification - Jian Cheng; Zhiwei Xu; Desheng Zhao; Mingyu Xie; Huihui Yang; Liying Wen; Kesheng Li; Hong Su (International Journal of Biometeorology, 2016)

Protective role of ACE2-Ang-(1–7)-Mas in myocardial fibrosis by downregulating KCa3.1 channel via ERK1/2 pathway - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2016)

Prevalence of bacterial resistance within an eco-agricultural system in Hangzhou, China - Like Xu; Yanyun Qian; Chao Su; Weixiao Cheng; Jianan Li; Mark L. Wahlqvist; Hong Chen (Environmental Science and Pollution Research, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Sporoschisma from submerged wood in Yunnan, China - Zong-Long Luo; Dan-Feng Bao; Jayarama D. Bhat; Jing Yang; Hong-Mei Chai; Shu-Hong Li; Ali H. Bahkali; Hong-Yan Su; Kevin D. Hyde (Mycological Progress, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Cadmium availability and uptake by radish (Raphanus sativus) grown in soils applied with wheat straw or composted pig manure - Hong Shan; Shiming Su; Rongle Liu; Shutian Li (Environmental Science and Pollution Research, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Salusin β Within the Nucleus Tractus Solitarii Suppresses Blood Pressure Via Inhibiting the Activities of Presympathetic Neurons in the Rostral Ventrolateral Medulla in Spontaneously Hypertensive Rats - Hong-Bao Li; Yan Lu; Jin-Jun Liu; Yu-Wang Miao; Tian-Zhen Zheng; Qing Su; Jie Qi; Hong Tan; Zu-Yi Yuan; Guo-Qing Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Myricetin protects against diet-induced obesity and ameliorates oxidative stress in C57BL/6 mice - Hong-ming Su; Li-na Feng; Xiao-dong Zheng; Wei Chen (Journal of Zhejiang University-SCIENCE B, 2016)

Impact of temperature variation between adjacent days on childhood hand, foot and mouth disease during April and July in urban and rural Hefei, China - Jian Cheng; Rui Zhu; Zhiwei Xu; Jinju Wu; Xu Wang; Kesheng Li; Liying Wen; Huihui Yang; Hong Su (International Journal of Biometeorology, 2016)

Reserpine Inhibit the JB6 P+ Cell Transformation Through Epigenetic Reactivation of Nrf2-Mediated Anti-oxidative Stress Pathway - Bo Hong; Zhengyuan Su; Chengyue Zhang; Yuqing Yang; Yue Guo; Wenjing Li; Ah-Ng Tony Kong (The AAPS Journal, 2016)

Removal of Two Species of Harmful Algae Using Gramine Modified Montmorillonite - Su-li Liu; Wen-wen Wang; Fei Liu; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Bulletin of Environmental Contamination and Toxicology, 2016)

Integrated simulation method for waterlogging and traffic congestion under urban rainstorms - Boni Su; Hong Huang; Yuntao Li (Natural Hazards, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Responses of endophytic and rhizospheric bacterial communities of salt marsh plant (Spartina alterniflora) to polycyclic aromatic hydrocarbons contamination - Jianqiang Su; Weiying Ouyang; Youwei Hong; Dan Liao; Sardar Khan; Hu Li (Journal of Soils and Sediments, 2016)

The association between diurnal temperature range and childhood bacillary dysentery - Li-ying Wen; Ke-fu Zhao; Jian Cheng; Xu Wang; Hui-hui Yang; Ke-sheng Li; Zhi-wei Xu; Hong Su (International Journal of Biometeorology, 2016)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Erratum to: Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Two genes conferring resistance to Pythium stalk rot in maize inbred line Qi319 - Feng-Jing Song; Ming-Gang Xiao; Can-Xing Duan; Hong-Jie Li; Zhen-Dong Zhu; Bao-Tao Liu; Su-Li Sun; Xiao-Fei Wu; Xiao-Ming Wang (Molecular Genetics and Genomics, 2015)

Water relations and gas exchange of fan bryophytes and their adaptations to microhabitats in an Asian subtropical montane cloud forest - Liang Song; Yong-Jiang Zhang; Xi Chen; Su Li; Hua-Zheng Lu; Chuan-Sheng Wu; Zheng-Hong Tan; Wen-Yao Liu; Xian-Meng Shi (Journal of Plant Research, 2015)

A comprehensive study of the impact of polycyclic aromatic hydrocarbons (PAHs) contamination on salt marsh plants Spartina alterniflora: implication for plant-microbe interactions in phytoremediation - Youwei Hong; Dan Liao; Jinsheng Chen; Sardar Khan; Jianqiang Su; Hu Li (Environmental Science and Pollution Research, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Bacterial community composition at anodes of microbial fuel cells for paddy soils: the effects of soil properties - Ning Wang; Zheng Chen; Hong-Bo Li; Jian-Qiang Su; Feng Zhao; Yong-Guan Zhu (Journal of Soils and Sediments, 2015)

Nanoparticulate TiO2 Protection of Midgut Damage in the Silkworm (Bombyx mori) Following Phoxim Exposure - Ling Wang; Mingyu Su; Xiaoyang Zhao; Jie Hong; Xiaohong Yu; Bingqing Xu; Lei Sheng; Dong Liu; Weide Shen; Bing Li; Fashui Hong (Archives of Environmental Contamination and Toxicology, 2015)

Response of vacuolar processing enzyme in Malus hupehensis and MhVPEγ-overexpressing Arabidopsis to high temperature stress - Qian Su; Kun Ran; Xiu-Jin Men; Wei-Wei Zhang; Shu-Lei Fan; Li-Juan Yan; Hong-Qiang Yang (Acta Physiologiae Plantarum, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Soil cellulase activity and fungal community responses to wetland degradation in the Zoige Plateau, China - Li-sha Wu; Su Feng; Yuan-yang Nie; Jian-hong Zhou; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2015)

LGI1 is Involved in the Development of Mouse Brain - Li-Da Su; Ya-Jun Xie; Liang Zhou; Ying Shen; Ying-Hong Hu (The Cerebellum, 2015)

Orbilia yuanensis sp. nov. and its anamorph - Min Qiao; Jian-Ying Li; Hans-Otto Baral; Ying Zhang; Wen-Yun Qian; Hong-yan Su; Ze-Fen Yu (Mycological Progress, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Histone methyltransferase G9a and H3K9 dimethylation inhibit the self-renewal of glioma cancer stem cells - Hong Tao; Haiying Li; Yanhuang Su; Danni Feng; Xilong Wang; Chun Zhang; Hui Ma; Qikuan Hu (Molecular and Cellular Biochemistry, 2014)

Estimation methods and monitoring network issues in the quantitative estimation of land-based COD and TN loads entering the sea: a case study in Qingdao City, China - Ying Su; Xiulin Wang; Keqiang Li; Shengkang Liang; Guodong Qian; Hong Jin; Aiquan Dai (Environmental Science and Pollution Research, 2014)

Dynamic alterations of connexin43, matrix metalloproteinase-2 and tissue inhibitor of matrix metalloproteinase-2 during ventricular fibrillation in canine - Jing Wang; Jing-sha Li; Hong-zhen Liu; Shao-lei Yi; Guo-ying Su; Yun Zhang; Jing-quan Zhong (Molecular and Cellular Biochemistry, 2014)

Transcript suppression of TaGW2 increased grain width and weight in bread wheat - Yantao Hong; Longfei Chen; Li-pu Du; Zhenqi Su; Jinfen Wang; Xingguo Ye; Lin Qi; Zengyan Zhang (Functional & Integrative Genomics, 2014)

Change and Significance of IL-8, IL-4, and IL-10 in the Pathogenesis of Terminal Ileitis in SD Rat - Hong-yu Zhou; Jun Yan; Li Fang; Hui Zhang; Li-guo Su; Guo-hua Zhou (Cell Biochemistry and Biophysics, 2014)

Regulation of synchronism by abscisic-acid-responsive small noncoding RNAs during somatic embryogenesis in larch (Larix leptolepis) - Jun-Hong Zhang; Shou-Gong Zhang; Shui-Gen Li; Su-Ying Han; Wan-Feng Li; Xin-Min Li; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Changes in water use with growth in Ulmus pumila in semiarid sandy land of northern China - Hua Su; Yonggeng Li; Wei Liu; Hong Xu; Osbert Jianxin Sun (Trees, 2014)

The post-transcriptional regulation of LaSCL6 by miR171 during maintenance of embryogenic potential in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Tree Genetics & Genomes, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

Frequency of HLA-A*03 associates with HIV-1 infection in a Chinese cohort - WeiLun Zhang; Li Wang; KunXue Hong; YanXin Liu; Bing Su; Cheng Xu; JianQin Xu; YuHua Ruan; YiMin Shao; DeXian Zheng (Science China Life Sciences, 2013)

Interleukin-17 and acute coronary syndrome - Sheng-an Su; Hong Ma; Li Shen; Mei-xiang Xiang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Retrograde cPLA2α/Arachidonic Acid/2-AG Signaling Is Essential for Cerebellar Depolarization-Induced Suppression of Excitation and Long-Term Potentiation - Li-Da Su; De-Juan Wang; Dong Yang; Ying Shen; Ying-Hong Hu (The Cerebellum, 2013)

Regulation of LaMYB33 by miR159 during maintenance of embryogenic potential and somatic embryo maturation in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Increased precipitation during the Little Ice Age in northern Taiwan inferred from diatoms and geochemistry in a sediment core from a subalpine lake - Liang-Chi Wang; Hermann Behling; Teh-Quei Lee; Hong-Chun Li; Chih-An Huh; Liang-Jian Shiau; Su-Hwa Chen; Jiunn-Tzong Wu (Journal of Paleolimnology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Polymorphisms of the interleukin-15 gene and their associations with fatness and muscle fiber traits in chickens - Shi-Jie Lv; Ling Su; Hong Li; Rui-Li Han; Gui-Rong Sun; Xiang-Tao Kang (Journal of Applied Genetics, 2012)

A label-free differential quantitative proteomics analysis of a TaLEA-introduced transgenic Populus simonii × Populus nigra dwarf mutant - Su Chen; Hong-mei Yuan; Gui-feng Liu; Hui-yu Li; Jing Jiang (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Identification and expression of a putative LPS-induced TNF-α factor from Asiatic hard clam Meretrix meretrix - Hong-jun Li; Qing Yang; Xiang-gang Gao; Hao Su; Juan Wang; Chong-bo He (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

Two novel mutations of the IRX4 gene in patients with congenital heart disease - Zhi Cheng; Jing Wang; Dongmei Su; Hong Pan; Guoying Huang; Xiaotian Li; Zhongzhi Li; Adong Shen; Xiaodong Xie; Binbin Wang; Xu Ma (Human Genetics, 2011)

Antithrombotic lipids from Semen Persicae - Nian-Yun Yang; Li Liu; Wei-Wei Tao; Jin-Ao Duan; Xun-Hong Liu; Su-Ping Huang (Natural Product Research, 2011)

Accurate assessment of antibiotic susceptibility and screening resistant strains of a bacterial population by linear gradient plate - YuQing Liu; JingRan Li; JiaFa Du; Ming Hu; Hua Bai; Jing Qi; Chao Gao; TianTian Wei; Hong Su; JianLing Jin; PeiJi Gao (Science China Life Sciences, 2011)

Activation of regulatory T cells instigates functional down-regulation of cytotoxic T lymphocytes in human breast cancer - Chao-Hsu Li; Wen-Hong Kuo; Wen-Chun Chang; Su-Cheng Huang; King-Jen Chang; Bor-Ching Sheu (Immunologic Research, 2011)

The complete mitochondrial genome of the hard clam Meretrix meretrix - Chong-bo He; Jian Wang; Xiang-gang Gao; Wen-tao Song; Hong-jun Li; Yun-feng Li; Wei-dong Liu; Hao Su (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Efficacy of Amifostine in Treating Patients with Idiopathic Thrombocytopenia Purpura - Hui Fan; Hong-Li Zhu; Su-Xia Li; Xue-Chun Lu; Bing Zhai; Bo Guo; Shan-Qian Yao; Yang Liu (Cell Biochemistry and Biophysics, 2011)

Quantitative assessment of climate change and human impacts on long‐term hydrologic response: a case study in a sub‐basin of the Yellow River, China - Jiahu Wang; Yang Hong; Jonathan Gourley; Pradeep Adhikari; Li Li; Fengge Su (International Journal of Climatology, 2010)
In this study we developed an impact factor formula (IFF) to quantitatively attribute separately the impacts of climate change and local human activities on hydrological response (i.e. run‐off) in a sub‐basin of Yellow River for the period 1950–2000. Using the daily climatic data, we first calibrated and verified the variable infiltration capacity (VIC) hydrological model to the baseline period 1955–1970. Then we developed the basin's natural run‐off for the following three decades (1971–2000) using the VIC model without considering local human impacts, as the VIC model is benchmarked by the 1960's hydrological regime. On the basis of observed precipitation, run‐off and reconstructed natural run‐off data from 1971 to 2000, we quantified their long‐term trend, decadal and annual variations. Using daily climatic observations, we showed that the precipitation and run‐off have decreased from the baseline decade, the 1960s, indicating a drier hydrological regime for recent decades. We further applied the IFF to quantitatively attribute separately the impacts of reduced precipitation and increased temperatures from climate change and then of local human activities on hydrological run‐off response. It was found that climate change has a greater impact than human activities on the basin's run‐off for the three consecutive decades. The pCC (percentage change of run‐off due to climate change impact) is found to be 89% followed by 66% and 56% in 1970s, 1980s and 1990s, respectively. Over the decades, pHA (percentage change of run‐off due to human activities) has continuously increased from 11% to 44%. If the trend continues, in future, the pHA is going to outweigh pCC in this basin. This study provides a quantitative assessment methodology for water resources managers to understand the changing process of the hydrological cycle and attribute its causative factors in a sub‐basin of the Yellow River. Copyright © 2009 Royal Meteorological Society

Influence of 14-day hind limb unloading on isolated muscle spindle activity in rats - Xue Hong Zhao; Xiao Li Fan; Xin Ai Song; Su Di Wu; Jun Chan Ren; Ming Xia Chen (Journal of Muscle Research and Cell Motility, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

RA induces the neural-like cells generated from epigenetic modified NIH/3T3 cells - Xi-Mei Zhang; Qiu-Ming Li; Dong-Ju Su; Ning Wang; Zhi-Yan Shan; Lian-Hong Jin; Lei Lei (Molecular Biology Reports, 2010)

Treatment strategies for Parkinson’s disease - Hong Yuan; Zhen-Wen Zhang; Li-Wu Liang; Quan Shen; Xiang-Dang Wang; Su-Mei Ren; Hong-Jie Ma; Shu-Jun Jiao; Ping Liu (Neuroscience Bulletin, 2010)

A novel mutation in the connexin 29 gene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Ching-Chyuan Su; Juan-Yu Chang; Tung-Cheng Li; Shuan-Yow Li (Human Genetics, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Leaf-level plasticity of Salix gordejevii in fixed dunes compared with lowlands in Hunshandake Sandland, North China - Hua Su; Yonggeng Li; Zhenjiang Lan; Hong Xu; Wei Liu; Bingxue Wang; Dilip Kumar Biswas; Gaoming Jiang (Journal of Plant Research, 2009)

Drepanocladus longifolius (Amblystegiaceae), an addition to the moss flora of King George Island, South Shetland Islands, with a review of Antarctic benthic mosses - Su-Ping Li; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Ming-Hong Cai; Hai-Ying Wang; Cheng-Sen Li (Polar Biology, 2009)

Effects of Nano-anatase TiO2 on Absorption, Distribution of Light, and Photoreduction Activities of Chloroplast Membrane of Spinach - Mingyu Su; Fashui Hong; Chao Liu; Xiao Wu; Xiaoqing Liu; Liang Chen; Fengqing Gao; Fan Yang; Zhongrui Li (Biological Trace Element Research, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Observation of amyloid precursor protein cleavage and Aβ generation in living cells by using multiphoton laser scanning microscopy - Xiao-Qing Li; Su-Ming Zhang; Hua-Jing Yang; Zhi-Hong Zhang (Neuroscience Bulletin, 2007)

Effects of Nano-anatase TiO2 on Absorption, Distribution of Light, and Photoreduction Activities of Chloroplast Membrane of Spinach - Su Mingyu; Hong Fashui; Liu Chao; Wu Xiao; Liu Xiaoqing; Chen Liang; Gao Fengqing; Yang Fan; Li Zhongrui (Biological Trace Element Research, 2007)

Rice Allelopathy Induced by Methyl Jasmonate and Methyl Salicylate - Hai Hong Bi; Ren Sen Zeng; Li Ming Su; Min An; Shi Ming Luo (Journal of Chemical Ecology, 2007)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

Developmental analyses reveal early arrests of the spore-bearing parts of reproductive organs in unisexual flowers of cucumber (Cucumis sativus L.) - Su-Lan Bai; Yi-Ben Peng; Ji-Xin Cui; Hai-Tao Gu; Li-Yun Xu; Yi-Qin Li; Zhi-Hong Xu; Shu-Nong Bai (Planta, 2004)

Production of two Highly Active Bacterial Phytases with Broad pH Optima in Germinated Transgenic Rice Seeds - Chwan-Yang Hong; Kuo-Joan Cheng; Tung-Hai Tseng; Chang-Sheng Wang; Li-Fei Liu; Su-May Yu (Transgenic Research, 2004)

A deletion mutation in the ?A1/A3 crystallin gene (CRYBA1/A3) is associated with autosomal dominant congenital nuclear cataract in a Chinese family - Yanhua Qi; Hongyan Jia; Shangzhi Huang; Hui Lin; Jingzhi Gu; Hong Su; Tieying Zhang; Ya Gao; Lijun Qu; Dandan Li; Ying Li (Human Genetics, 2004)

DNA damage in the early primordial anther is closely correlated with stamen arrest in the female flower of cucumber ( Cucumis sativus L.) - Yu-Jin Hao; Dong-Hui Wang; Yi-Ben Peng; Su-Lan Bai; Li-Yun Xu; Yi-Qin Li; Zhi-Hong Xu; Shu-Nong Bai (Planta, 2003)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)